Lipid-lowering activity of mulberry seed unsaturated fatty acids: integrating network pharmacology and experimental validation - Yue Zhang; Haoran Huang; Jianglong He; Yuqi Li; Xueping Jiang; Ping Wu; Syed Asim Shah Bacha; Ran Zhang; Hao Li; Gaiqun Huang; Zhongzheng Gui (Functional & Integrative Genomics, 2026)

Erosion and entrainment in dry granular flows: Insights from large-scale experiments - Shi-lin Zhang; Yang Gao; Yue-ping Yin; Lonneke Roelofs; Wen-pei Wang; Xie-wen Hu; Bin Li (Engineering Geology, 2026)

Orbitally driven ammonium upwelling fueled primary productivity during the peak Cambrian Explosion - Guangming Meng; Haifeng Gai; Chengang Lu; Yanming Zhao; Yineng Tan; Yang Liu; Yue Feng; Gang Li; Xing Wang; Wei Liu; Yijie Xing; Ping Gao; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Divergent responses of ecosystem water use efficiency to environmental drivers in arid versus humid regions - Hailing Li; Maohong Wei; Hongling Yang; Ya Hu; Shaokun Wang; Ping Yue; Xujun Ma; Fangwei Hao; Rong Ma; Xiaoan Zuo (Journal of Environmental Management, 2026)

Efficient antibiotic degradation by concentrated solar activation of trichloroisocyanuric acid: The role of triplet-state-mediated singlet oxygen generation - Yue Yang; Li Tang; Kun Chen; Ping Chen; Yixun Zheng; Bingbing Liu; Jin Wu; Shimin Zhou; Yongpeng Zhang; Yuxin Xian; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Discovery of spiroindolediketopiperazine alkaloids from Penicillium sp. KYS-32 as dual inhibitors of ABCB1 and ABCG2 to reverse multidrug resistance - Yu-Lei Zhu; Ying Li; Xiang-Yu Liu; Yan-Ping Zhu; Jian-Min Yue; Jin-Hai Yu (Phytochemistry, 2026)

Long-range transported dust enhances ice nucleating particle abundance in the North China Plain - Yue Sun; Yujiao Zhu; Hengde Liu; Lanxiadi Chen; Hongyong Li; Yujian Bi; Di Wu; Xiangkun Yin; Can Cui; Ping Liu; Yu Yang; Jisheng Zhang; et al. (Journal of Environmental Sciences, 2026)

An innovative immobilization-free homogeneous electrochemical strategy facilitated by buoyancy -magnetism separation for evaluating the acetamiprid in food - Ya-Rong Xie; Yue-Han Wang; Jia-Le Wang; Li-Ping Jia; Wei Zhang; Lei Shang; Xiao-Jian Li; Qing-Wang Xue; Huai-Sheng Wang; Rong-Na Ma (Food Chemistry, 2026)

Stable isotope labeling LC–MS for profiling the amine submetabolome in a D-lactate treated cell model - Yue-Qiang Chen; Xiao-Xia Dong; Li Liu; Xiu-Ping Chen; Chen-Guo Feng; Li-Xing Zhan; Yue Su; Fang Zhang; Yin-Long Guo (Analytica Chimica Acta, 2026)

Research on tunnel construction quality control based on blockchain technology and Bayesian networks - Li-ping Cai; Qiaona Gong; Feng Jiang; Mingzhan Yuan; Zhiyong Xiao; Shuai Zhang; Chengcheng Zheng; Yue Wu (Applied Geophysics, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

Spatiotemporal variability, driving factors, and potential human health risks of fluoride and nitrate in surface water and groundwater of a sandy desert lake basin, Northwest China - Xiangwei Li; Muhan Li; Shen Qu; Keyi Zhang; Yuanzhen Zhao; Ao Gao; Renpu Wang; Dongchao Huo; Zongbao Yue; Bowen Ye; Hongli Ma; Ping Miao; et al. (Journal of Environmental Sciences, 2026)

Preparation of C and Co co-doped TiO2 Nanomaterials for Visible-Light Photocatalytic Antibacterial Activity - Chunhui Meng; Yuena Li; Qitong He; Yue Hao; Wenjun Yin; Huang Zhou; Ping Li (Water, Air, & Soil Pollution, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Different land use types around megacities contribute contrasting heavy metal pollution and health risks in soil-leaf vegetable systems - Ling Huang; Wen-Fei Chen; Yue-E Guan; Yan-Ping Pang; Sheng-Gong Yu; Lin Li; Qi Zou; Meng-Qiang Sun; Hang Wei; Zhi-Liang Chen (Environmental Research, 2026)

CdS incorporation induced gate-opening in UiO-66-NH2 for photocatalysis - Qi Li; Bryan Kit Yue Ng; Zhao-Xue Luan; Ping-Luen Baron Ho; Daniel Woodside; Xiyu Zhang; Christopher Foo; Pu Zhao; Tai-Sing Wu; Yun-Liang Soo; Mingjie Li; Xin-Ping Wu; et al. (Chemical Engineering Journal, 2026)

Tailored pore engineering in crystalline COF membranes via trimesoyl chloride cross-linking for high-performance pharmaceutical nanofiltration in water treatment - Hao Wang; Lian You; Jian-wei Jia; Yi Wang; Li-ping Yue; Fan-xin Kong (Chemical Engineering Journal, 2026)

A Novel Wave-Absorbing Support System for Mitigating Rock Burst in Deep-Buried Hard Rock Tunnels - Yue-Mao Zhao; Zheng-Chen Ge; Ben-Guo He; Cheng-Xiang Yang; Xing-Long Li; Xiao-Jun Yu; De-Xian Li; Yong-Ping Liu (Rock Mechanics and Rock Engineering, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Overcoming gastrointestinal mucosal barriers: Mechanistic innovations and technical advances in mucosal targeting strategies for animal oral vaccines - Meijun Yu; Yue Li; Zhaojun Wang; Ping Han; Yanping Jiang; Wen Cui; Yijing Li; Lijie Tang; Shuo Jia; Hongzhe Zhao; Yingying Ma; Jiaxuan Li; et al. (Veterinary Microbiology, 2026)

Structural dynamics of chloroplast genome in Paphiopedilum (Orchidaceae): in response to natural hybridization - Xue-Ying Wei; Ai-Qun Hu; Jin Zhou; Jiang-Ping Shu; Wei-Yue Sun; Li-Qiang Li; Jian-Wen Shao; Hui Wang; Yue-Hong Yan (Molecular Phylogenetics and Evolution, 2026)

Assessment of commercial NF membranes for selective separation of Mg2+/Li+ in simulated brines - Tian-tian Xue; Jian-wei Jia; Fan-xin Kong; Li-ping Yue; Guang-dong Sun; Jin-fu Chen (Journal of Water Process Engineering, 2026)

Distribution, source, and pollution risk assessment of heavy metals in the coastal sediments of the northern South China sea - Wen Yu; Yuqing Fan; Qinghua Chen; Jing Yang; Xin Li; Wei Huang; Kun Yue; Liuyi Zhang; Ping Ding; Guocheng Hu; Yunjiang Yu (Environmental Pollution, 2026)

Shrub Encroachment Constrains Precipitation‐Driven Shifts in Herbaceous Biomass‐Diversity Relationships - Hailing Li; Xiaoan Zuo; Fons van der Plas; Ya Hu; Fangwei Hao; Hongling Yang; Xiangyun Li; Ping Yue; Shaokun Wang; Zhaobin Song; Rentao Liu; Jiansheng Ye; et al. (Global Change Biology, 2026)
The relationship between herbaceous above ground biomass and species richness typically exhibits a unimodal pattern, shifting from positive under low‐precipitation conditions to negative under high‐precipitation conditions. While shrub encroachment generally reduces both herbaceous aboveground biomass and diversity, how shrubs mediate the herbaceous biomass‐richness relationship under altered precipitation regimes remains unclear. By synthesizing data from globally distributed precipitation manipulation experiments, we reveal contrasting herbaceous biomass‐diversity responses in grasslands and shrublands. In grasslands, reduced precipitation shifts the peak of the unimodal herbaceous biomass‐richness curve toward lower biomass, whereas increased precipitation shifts it toward greater biomass. In contrast, the peak of the unimodal relationship in shrub‐dominated systems shows no significant shifts across precipitation extremes. These global patterns are supported by a 5‐year field experiment in a desert steppe in Northern China, which further shows that precipitation change strongly affects species richness through soil water availability in grasslands, while exerting weaker effects through modifications of the fast‐slow leaf economics spectrum in shrublands. These findings demonstrate that shrub encroachment can constrain precipitation‐induced changes in herbaceous biomass‐diversity relationships, providing important insights into how woody plant expansion interacts with climate change to influence ecosystem structure and function.

Predicting distribution characteristics of PM2.5 concentrations across China combining land use regression model and spatiotemporally weighted stacking machine learning algorithms - Wentao Wang; Ping Zhang; Yuanyuan Han; Fengqian Zhang; Yue Huang; Jinbao Liu; Ying Pan; Wenping Liu; Jian Chen; Mingyao Li; Yong Wang; Yefan Jia; et al. (Journal of Environmental Chemical Engineering, 2026)

Sustainable pathways for pig farming in China: Life cycle assessment of manure management systems and environmental optimization - Xinyue Dong; Ping Wang; Yingping Li; Yafei Wang; Zhepu Ruan; Bing Wu; Yue Wang; Zhuobiao Ni; Rongliang Qiu (Journal of Environmental Management, 2026)

Why Does Braising Enhance the Aroma Profile of Xinjiang Braised–Roasted Chicken? Insights into Precursor Conversion and Aroma Formation Pathways - Ke Bi; Yue Liu; Dong Han; Xinwei Li; Yinfeng Lei; Hong Pan; Ping Yang; Chunhui Zhang; Marie-laure Fauconnier (Food Research International, 2026)

Immobilization and magnetic removal of lead in contaminated soils using a waste-derived magnetic molecular sieve - Chang Lei; Xiu-Ru Xie; Lai-Shou Long; Rui Li; Zhi-Ping Fu; Zhi-Yue Zhao (Journal of Soils and Sediments, 2026)

General Biogeographic Rules and Lineage‐Specific History Shape the Assembly of Asian Tropical Megadiversity - Hao Wu; Bing‐Yue Zhu; Jing Yang; Qiang Zhang; Zhen‐Ping Shi; Yan‐Jing Shi; Xiao‐Chen Zhao; Pei‐Yi Yang; Ke‐Xin Fan; Guang‐Shun Li; Si‐Qi Hu; Yee Wen Low; et al. (Journal of Biogeography, 2026)
Aim Tropical Asia's extraordinary plant diversity is thought to be intrinsically linked to its dynamic geological history. However, quantifying the precise evolutionary processes that assembled this diversity across the archipelago remains challenging. A recently proposed biogeographic framework classifies the functional roles of different regions as “radiators,” “incubators,” “corridors” or “accumulators,” offering a useful framework to analyse this complexity. Here, we aim to provide a critical, independent test of this framework using the megadiverse tree genus Syzygium as a model system. Syzygium originated on the Sahul Shelf, contrasting with the Indochinese origin of rattan palms used in the original framework validation. Location Tropical Asia, Pacific Islands and Africa. Methods We analysed the complete chloroplast genome of 200 species of the genus Syzygium and performed phylogenetic analysis to estimate divergence times, ancestral region reconstruction, and estimated diversification and extinction rates. We then analysed the relationship between regional area and the dispersal of species and examined speciation and dispersal patterns in relation to the geographical environment. Results Our comprehensive chloroplast phylogenomic analysis indicates rapid diversification of Syzygium commencing ~12 million years ago, coinciding with shelf collision. Biogeographic reconstructions indicate that while the framework's general principles hold – continental shelf act as “radiators” and isolated islands as “incubators” – the specific geographic roles vary depend on lineage history . Main Conclusions Our study validates the radiator‐incubator model as a general feature of tropical Asian evolution but refines it by demonstrating that historical contingency is key to understanding the assembly of Earth's richest biota. Tropical Asian plant diversity reflects a unique geological history of continental shelf collision and dynamic island geography, offering insights into biodiversity evolution in other geologically active regions worldwide, highlighting the importance of maintaining large, connected natural areas and dispersal corridors for preserving the evolutionary processes that generate Earth's botanical richness.

Physicochemical strategies for antibiotic removal in aquaculture wastewater: Mechanistic insights, technological challenges, and sustainable development pathways - Tai-Yue Wang; Yan-Ping Qiao; Kai-Jun Yue; Ming Cheng; Li-Ting Hao; Nan Zhang; Ran-Bin Liu; Chen Shi (Aquaculture, 2026)

Research on spontaneous combustion thermal generation and transfer effects of coal–based activated carbon and its precursors - Hui-Fei Lyu; Fu-Xing Shen; Yue Li; Cai-Ping Wang; Jun Deng; Wei-Feng Wang (Process Safety and Environmental Protection, 2026)

Diapause termination alters the m6A methylation profiles and regulates gene expression associated with early embryonic development in the silkworm (Bombyx mori) - Zhi-Hao Huang; Jia-Yue Yang; Cai-Ping Hou; Shi-Huo Liu; Bing Li; Jie Wang; Shou-jun Huang; Jia-Ping Xu (Journal of Insect Physiology, 2026)

Microscopic mechanisms of dissolved organic matter sequestration and transformation at the mineral-water interfaces during the formation and transformation of Fe Mn (hydr)oxides - Kai Cui; Libin Wu; Zihao Wu; Yue Yang; Shiwen Hu; Xiaoyuan Zhang; Zilong Zeng; Ping Chen; Li Wang; Zecong Ding; Hao Yi (Chemical Engineering Journal, 2026)

Oligosaccharide mapping analysis through UPLC-Orbitrap-HRMS and enzymatic hydrolysis from Polygonatum odoratum (Mill.) Druce - Qing-Hua Liu; Liu Yang; Yue Wang; Hao-Ming Xiong; Cai-Yun Wang; Guo-Yuan Zhu; Li-ping Bai; Zhi-Hong Jiang; Wei Zhang (Carbohydrate Polymers, 2026)

Influence of winter stratospheric polar vortex intensity on spring drought in northern China - Jinyu Zhang; Ping Yue; Qiang Zhang; Jinhu Yang; Pengcheng Yan; Suping Wang; Hong Li (Climate Dynamics, 2026)

The Classification History of Lamiaceae and a Generic Synopsis in China - Si-Cheng Xu; Su Liu; Ya-Ping Chen; Yue Zhao; Fei Zhao; Chun-Lei Xiang; Bo Li (The Botanical Review, 2026)

Reliable Rock Mass Classification for Tunneling: Hole-Level MWD Data Modeling with Cost-Sensitive Bagging - Yue-ming Yuan; Jin-rui Duan; Zhao Han; Yi-guo Xue; Zhi-ping Sun; Fan-meng Kong; Chuan-gui Li (Applied Geophysics, 2026)

Nitrogen conversion and Feammox potential driven by microorganisms around the iron ore tailings pond - Yifan Jiang; Zhengbo Yue; Jin Wang; Ziyi Li; Xin Pan; Qinglong Guo; Zhiguo Li; Ping Guo; Ding Ma (Environment, Development and Sustainability, 2026)

Molecular insight into the structure and formation mechanism of fluid phase in the classical coking theory - Bo Gong; Jie-Ping Wang; Hao-Dong Liu; Rui Guo; Jin-Xiao Dou; Guang-Yue Li; Ying-Hua Liang (Fuel, 2026)

Dynamic temperature sensitivity improves simulated ecosystem respiration in a coupled land-atmosphere model - Tuanhui Wang; Yue Zhang; Ping Jiang; Longhui Li (Ecological Modelling, 2026)

A novel flexible branch-pinecone nanostructured UiO-66-MCA composite nanofiber membrane with bacteriostatic property for effective removal of salicylic acid - Yue Li; Jie Wang; Ping Lin; Shushu Jia; Lijuan Li; Yongxin Li; Ce Wang; Xiang Li (Water Research, 2026)

Spatiotemporal changes in dissolved organic matter chemodiversity and its interaction with microbial composition in heavy-metal polluted river - Chun Liu; Rujie Li; Yuheng Zhang; Lijie Zhang; Zhaoling Liu; Ping Li; Guanghui Fan; Yingjie Zhu; Yue Zuo; Xule Liu; Zhiyong Fu; Xiufeng Zhang (Water Research, 2026)

The appearance of microblade technology at the onset of Marine Isotope Stage 2 in Northeast China - Wei Liu; Jian-Ping Yue; You-Qian Li; Ke-Liang Zhao; Si-Qi Lu; Guang-Yi Bai; Yang Liu; Yu-Xiu Zhang; Shi-Xia Yang (Quaternary Science Reviews, 2026)

Iron-ceramsite with balanced electron transfer capacity enables simultaneous removal of refractory organics and nitrogen in coking wastewater by single-stage BAF - Hui Zhai; Ding Ma; Jin Wang; Wusong Xu; Yifan Jiang; Bixuan Sheng; Qinglong Guo; Zhiguo Li; Ping Guo; Zhengbo Yue (Chemical Engineering Journal, 2026)

Araloside A Induces Raf/MEK/ERK-Dependent Autophagy to Mitigate Alzheimer’s and Parkinson’s Pathology in Cellular and C. elegans Models - Xue Chen; Xing-Yue Zhou; Cai Lan; Hai-Jun Fu; Zhi-Chao Li; Meng-Yi Chen; Yong-Ping Wen; Lu Yu; Da-Lian Qin; An-Guo Wu; Jian-Ming Wu; Xiao-Gang Zhou (Molecular Neurobiology, 2025)

CsAHL20 negatively regulates epi-catechins biosynthesis under drought stress in Camellia sinensis - Yu Chen; Mingyuan Luo; Ping Li; Qi Zhao; Luo Chao; Yujie Jiao; Shiyu Tian; Xingyu Tian; Shenyuan Ye; Zhenkedai Yuan; Yilan Hu; Yongqing Bai; et al. (Plant Science, 2025)

Ferrous sulfate and low aeration improve carbon component quality in chicken manure compost by regulating the tricarboxylic acid cycle and promoting humification - Chaonan Pan; Yue Zhao; Nina Zhu; Ping Ren; Sainan Li; Yue Li; Zimin Wei (Journal of Environmental Management, 2025)

Electrospun Mn-doped ZIF-67 composite nanofibers with high water stability for efficient adsorption of antibiotics in aqueous systems - Xiaolin Yue; Can Cui; Shaolin Deng; Lan Wang; Ping Li; Anhong Li; Yizhong Zhang; Rui Hao; Wenyuan Tan (Journal of Environmental Chemical Engineering, 2025)

Bacterial outer membrane vesicles encapsulated cationic polymer with STING agonist as nanovaccines for enhanced immunotherapy - Xiao-Li Tian; Ping Chen; Yue Hu; Lan Zhang; Jin Li; Ji Zhang (Chemical Engineering Journal, 2025)

Impact of Phosphate Solubilizing Bacterial Agent on Cadmium Bioavailability and Microbial Communities in Soil and Cd Accumulation in Lettuce Plants - Yue Yu; Ping Li; Yanhong Wang; Xinzhe Lu; Chunlei Huang; Hanqin Yin (Journal of Earth Science, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

The migration and transformation behavior of mercury and sulfur during coal pyrolysis - Caixia Yue; Yaning Zhu; Huijun Chen; Yahui Wang; Lunjing Yan; Ping Li; Xingjun Wang; Meijun Wang; Liping Chang; Weiren Bao; Jiancheng Wang (Fuel, 2025)

Osthole inhibits proliferation and induces autophagy-dependent ferroptosis of cervical cancer cells through induction of TFR1 - Linjun Li; Yue Zhao; Xiaojuan Li; Muzhao Tian; JiaoQing Wei; Wanyu Xie; Caishan Liu; Ping Dai; Juan Wang (Food and Chemical Toxicology, 2025)

Internal encapsulation for enhancing perovskite solar cell stability based on moisture-triggered in situ polymerization - Jingwei Zhu; Jianting Huang; Ping Hu; Wei Yue; Mingdeng Wei; Ying Zhang; Yafeng Li (Chemical Engineering Journal, 2025)

Interfacial electron accumulation of Ir-Co3O4 toward efficient acidic oxygen evolution reaction - Aiying Song; Chao Cai; Ming Jiang; Pengcheng Li; Ping Liao; Yue Huang; Lang Chen; Xuming Yang; Yuanmin Zhu (Chemical Engineering Journal, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Visualization of MC-LR in lakes using near-infrared technology - Huiyan Chuan; Bingyan Li; Zhaomin Wang; Yue Zhang; Ping Xie; Yong Liu (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Self-reinforcing extraction of uranium(VI) from wastewater via uranium-incorporated hematite photoelectrochemical system - Jiacheng Wu; Jingjing Wang; Yueran Qi; Zena Zhang; Yue Li; Fan Chen; Ping Li; Yuheng Wang (Journal of Hazardous Materials, 2025)

Biogenic amine-responsive ratiometric fluorescent microneedle sensor for real-time visualization of meat freshness - Li-Jian Chen; Jiang-Yue Wang; Xu Zhao; Xiu-Ping Yan (Food Chemistry, 2025)

Intercropping enhances the reciprocal facilitation of N and P uptake through complementarity - Hao-Yue Qin; Cheng-Bao Wang; Ping Wang; Si-Cun Yang; Xiao-Fei Li; Long Li (Plant and Soil, 2025)

Integrating ecological niche and epidemiological models to predict wheat fusarium head blight using remote sensing and meteorological data - Shangzhou Li; Ping Dong; Hui Zhang; Xin Xu; Lei Shi; Tong Sun; Hongbo Qiao; Jibo Yue; Wei Guo (Computers and Electronics in Agriculture, 2025)

Selective and controllable mechanism of the temperature field in skin tissue under radiofrequency heating: finite element analysis and ex-vivo pig skin experiments - Ping Zhu; Chuanqi Xie; Kai Li; Fangjie Shu; Liqiang Li; Zhaodi Su; Yue Xue (Journal of Thermal Biology, 2025)

Genetic diversity assessment and disease resistance gene identification of Yunnan rice landraces - Mei Li; Rongping Li; Yunxiu Yang; Xiaoqiao Zhu; Huiling Zhang; Yun-Yue Wang; Ping He; Guangyu Han (European Journal of Plant Pathology, 2025)

Bioinspired copper-doped covalent organic polymers with laccase-mimicking activity for on-site monitoring of thiram in fruit and vegetable samples - Ya Di Shi; Meng Ping Wang; Han Wu; Sai Jin Xiao; Zi Yang Yue; Ding Zhong Yuan; Xin Xin Shao; Feng Tao Yu; Li Zhang (Analytica Chimica Acta, 2025)

Anthropogenic nitrogen inputs favour increased nitrogen and organic carbon levels in Qinghai–Tibetan Plateau lakes: Evidence from sedimentary records - Ping Zhang; Xiangzhong Li; Fu-Jun Yue; Yuyan Zhang; Yuan Wang; Deyan Wu; Dongkun Liu; Fang Li; Xin Wang; Xuefang Ji (Water Research, 2025)

Early Eocene Metasequoia and Taxodium (Cupressaceae) from Lingbao, Henan Province and their implication for a perhumid climate in central China - Ping Liu; Hui Jia; Li Xu; Yu Li; Ming-Yue Luo; Tian-Qi Dong; Jiao Huang; Cheng Quan (Palaeoworld, 2025)

Recent advances and future research directions in the study of land-atmosphere interaction in northern China since the beginning of the 21st century - Qiang Zhang; Rong Wang; Ping Yue; Hongyu Li; Sheng Wang; Jian Zeng; Liang Zhang; Zesu Yang; Suping Wang; Jie Zhang; Liang Qiao; Hongli Zhang; et al. (Science China Earth Sciences, 2025)

Olaparib reverses prostate cancer resistance to Rapamycin by promoting macrophage polarization towards the M1 phenotype - Kai Ye; Gang Shi; Jian Xu; Kunyan Qiao; Qinghai Dai; Zhixiao Huo; Yu Cao; Wei Liu; Yue Hu; Lihua Yan; Yu Zhu; Ping Li; et al. (Molecular and Cellular Biochemistry, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Mesenchymal stem/stromal cells-derived exosomes: possible therapeutic mechanism in inflammatory bowel disease - Zekun Li; Luyun Liu; Yuhui Sun; Xinjuan Liu; Ping Zhang; Yue Wang; Gang Ding (Human Cell, 2025)

Spatial variability of lacustrine groundwater discharge and pollutant fluxes in the sandy-land lake group basins: Influence from land use types - Shen Qu; Xiangwei Li; Ao Gao; Yuanzhen Zhao; Keyi Zhang; Yiwei Zhang; Dongchao Huo; Bowen Ye; Zongbao Yue; Renpu Wang; Hongli Ma; Ping Miao; et al. (Journal of Environmental Management, 2025)

Gradient-Structured sodiophilic skeleton integrated with spatial confinement effect Enables high-rate and ultra-stable Na metal batteries - Fang-Yu Tao; Dan Xie; Wan-Yue Diao; Chang Liu; Godefroid Gahungu; Wen-Liang Li; Jing-Ping Zhang (Chemical Engineering Journal, 2025)

Development of a shear strengthening conductive hydrogel for impact protection and distress signal emission - Juan Tan; Xi Li; Chuan Ru Zheng; Anna Tan; Xiu Chen Li; Hai Liang Ni; Wen Hao Yu; Yue Feng Bai; Ping Hu; Hong Mei Chen (Chemical Engineering Journal, 2025)

Anti-hypoxia polyacetylenes and sesquiterpenoids from Codonopsis pilosula (Franch.) Nannf - Zhuo-Yang Cheng; Jun-Ge Jin; Meng Yan; Xin-Yue Chen; Jian-Kuan Li; Jian-Ping Gao; Jiang-Tao Zhou (Natural Product Research, 2025)

Four new constituents from the fruits of Cyclocodon lancifolius (Roxburgh) Kurz - Meng-Jie Ma; Wei Wu; Bei Tian; Li-Ping Shen; Tong Wu; Chun-Yue Huang; Xu-Dong Mao; Xiao Hu (Natural Product Research, 2025)

Preparation of electrospun ZIF-67/PVP/PVDF composite nanofiber membranes for efficient tetracycline removal from water - Shaolin Deng; Jing Zhang; Xiaolin Yue; Ping Li; Anhong Li; Zehua Huang; Wenyuan Tan (Journal of Environmental Chemical Engineering, 2025)

Regeneration of in vitro plants through direct and indirect organogenesis from Dracocephalum rupestre leaf explants - Jia li Wang; Kang jie Yue; Hui xin Liu; Xu ping Tian (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Aberrance of GAP43/p-GAP43 Closely Associates with the Pathology of Neuron Loss in Prion-Infected Rodent Models - Xiao-Xi Jia; Cao Chen; Chao Hu; Yue-Zhang Wu; Zhi-Yue Chao; Jia-Feng Zeng; Ru-Han A.; Dong-Hua Zhou; Yuan Wang; Wei-Wei Zhang; Kang Xiao; Li-Ping Gao; et al. (Molecular Neurobiology, 2025)

Sus scrofa RNase L inhibits PRRSV replication by activation of type I IFN signaling pathway and apoptosis - Xiangju Wu; Xiaoyan Cong; Ping Jiang; Mingming Zhou; Ying Yu; Dandan Jiang; Yue Hu; Juntong Li; Jinxia Zhang; Ying Cao; Haowen Zhang; Yijun Du; et al. (Veterinary Microbiology, 2025)

miRNA-125a regulates porcine oocyte maturation in vitro by targeting ADAR - Yue Han; Ping Lu; Yongsheng Yu; Weiyu Gu; Chunyu Li; Yanqiu Lv; Xinglin Qu; Yuyang Zhang; Qinglong Xu; Shunfa Yao; Xuan Chen; Yi Jin (Theriogenology, 2025)

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

Interactions between riverine sediment organic matter molecular structure and microbial community as regulated by heavy metals - Ping Li; Chun Liu; Lijie Zhang; Zhaoling Liu; Zhiyong Fu; Guanghui Fan; Yingjie Zhu; Yue Zuo; Liqiong Li; Lisha Zhang (Journal of Hazardous Materials, 2025)

Multifunctional flexible MXene/TA@CNC electronic hydrogel patch with robust adhesion and self-healing properties for wearable electronics - Haoyu Wang; Ping Han; Ying Yu; Shaolong Han; Yue Qiao; Yuehan Li; Bin Sun; Zheng Gu (Chemical Engineering Journal, 2025)

Estradiol Enhances Cerebellar Molecular Layer Interneuron-Purkinje Cell Synaptic Transmission and Improves Motor Learning Through ER-β in Vivo in Mice - Yong-Rui Piao; Mei-Rui Li; Ming-Ze Sun; Yang Liu; Chao-Yue Chen; Chun-Ping Chu; Yuki Todo; Zheng Tang; Chun-Yan Wang; Wen-Zhe Jin; De-Lai Qiu (The Cerebellum, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Revisiting the high temperature Darongshan-Shiwandashan granitoids in the South China: A response to slab tearing associated with diachronous collision between Indochina and South China blocks - Yu-Fan Yue; Xiao-Ping Xia; Pengfei Li; Bin He; Touping Peng; Min Sun; Jian Xu; M.P. Manu Prasanth (Lithos, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

The effect of nitrogen input on methane uptake in a wet and a dry year from a temperate desert steppe - Ping Yue; Kaihui Li; Ya Hu; Jingjuan Qiao; Zhaobin Song; Shaokun Wang; Tom Misselbrook; Xiaoan Zuo (Agricultural and Forest Meteorology, 2025)

Hydrogeochemical mechanism of Li-Cs-rich thermal springs in the Karakoram Fault, Qinghai-Xizang Plateau: New insights from multiple stable isotopes - Sheng Pan; Ping Zhao; Haichao Zhang; Zhaoying Yang; Yanyan Li; Yahui Yue; Xiaoming Liu; Shaopeng Gao; Yali Sun; Ji Dor (Science of The Total Environment, 2025)

Structurally diversified sesquiterpenoids from Chloranthus henryi and their neuroprotective activities on H2O2 damaged PC12 cells - Meng-Li He; Lian-Lian Xu; Yang Liu; Yan-Ping Gao; Yong-Ming Luo; Rong-Cai Yue; Fang-You Chen (Phytochemistry, 2025)

Conventional and biodegradable microplastics affected arsenic mobility and methylation in paddy soils through distinct chemical-microbial pathways - Hai-Qian Li; Jin-Peng Lv; Yue-Hui Jia; Jie Liu; Qiong Liang; Jian Zhou; Ai-Zhen Yang; Teng Yan; Yu-Ping Yang; Gui-Lan Duan (Journal of Hazardous Materials, 2025)

Overall solar H2O2 generation in water and real seawater by covalent organic frameworks with kgd topology - Jie-Yu Yue; Li-Ping Song; Zi-Xian Pan; Min Cheng; Xuan Wang; Qing Xu; Peng Yang (Chemical Engineering Journal, 2025)

Abundant surface adsorbed oxygen species originated from defect/vacancy sites during preferential CO oxidation - Yang Liu; Kunming Hou; Zhihua Guo; Yan Guo; Yue Jiang; Xinya Wu; Zewei Fu; Heng Zhang; Ping Li; Shanghong Zeng (Chemical Engineering Journal, 2025)

Sevoflurane postconditioning mitigates neuronal hypoxic-ischemic injury via regulating reactive astrocytic STAT3 protein modification - Yufei Jia; Yanhong Song; Hang Xue; Xingyue Li; Yinong Zhang; Shiyue Fan; Xu Yang; Zixuan Ding; Yue Qiu; Ziyi Wu; Ping Zhao (Chemico-Biological Interactions, 2025)

Precipitation-induced biomass enhancement and differential allocation in Inner Mongolia's herbaceous and shrub communities - Xiangyun Li; Ya Hu; Zhaobin Song; Ping Cong; Huan Cheng; Xuebo Zheng; Wenjing Song; Ping Yue; Shaokun Wang; Xiaoan Zuo (Science of The Total Environment, 2024)

Potential ecological risk assessment for trace metal(loid)s in soil surrounding coal gangue heaps based on source-oriented - Jie Ma; Zhijie Shen; Yue Jiang; Ping Liu; Jing Sun; Mingsheng Li; Xue Feng (Science of The Total Environment, 2024)

Discovery of polyoxygenated briaranes from octocoral Briareum stechei - Yue-Wen Chuang; Wei-Chen Ting; Su-Ying Chien; Li-Guo Zheng; Chih-Yin Huang; Zhi-Hong Wen; Yu-Jen Wu; Junichi Tanaka; You-Ying Chen; Jui-Hsin Su; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Sediment source-to-sink patterns along the southeast China coast during the late Quaternary: New insights from sediment geochemistry and OSL ages in Ningde Bay - Ping Liu; Jie Zhang; Yan Liu; Qianli Sun; Dan Zhang; Yue Li; Taoyuan Wei; Junjie Yu; Jilong Wang; Jing Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Effects of phosphate-solubilizing fungus Aspergillus flavus AF-LRH1 on promoting phosphorus solubilization, wheat growth and soil heavy metal remediation - Kaili Xu; Xiaoyong Lv; Feixue Yue; Lan Zhang; Ping Wang; Isaac Dennis Amoah; Kuok Ho Daniel Tang; Yiqing Yao; Ronghua Li (Journal of Environmental Chemical Engineering, 2024)

Unraveling anti-aging mystery of green tea in C. elegans: Chemical truth and multiple mechanisms - Jia-ping Ke; Jia-Yi Li; Zi Yang; Hao-Yue Wu; Jing-Ya Yu; Yi Yang; Chen-Hui Chen; Peng Zhou; Fang Hua; Wei Wang; Fenglin Hu; Gang-Xiu Chu; et al. (Food Chemistry, 2024)

Effects of fish skin collagen peptide on physicochemical properties of frozen dough and quality and antioxidant activity of steamed bread - Peiyao Li; Jinying Guo; Can Lu; Chonghui Yue; Ping Wang (Food Hydrocolloids, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

A novel mutation in hERG gene associated with azithromycin-induced acquired long QT syndrome - Yun-Jiu Cheng; Yang Wu; Hui-Qiang Wei; Yi-Jian Liao; Li-Ping Qu; Yue-Han Pan; Li-Juan Liu; Wen-Tao Bi (Molecular Biology Reports, 2024)

8-Br-cGMP suppresses tumor progression through EGFR/PLC γ1 pathway in epithelial ovarian cancer - Min Wu; Chunyan Mu; Huiwen Yang; Yue Wang; Ping Ma; Shibao Li; Zhongcheng Wang; Ting Lan (Molecular Biology Reports, 2024)

Rapamycin protects mouse skin from ultraviolet B-induced photodamage by modulating Hspb2-mediated autophagy and apoptosis - Ang Li; Ai-Jun Chen; Jing Xu; Zhu-Yuan Wen; Gen-Long Bai; Zi-Yue Wang; Yu-Xin Jiang; Ping Wang (Molecular Biology Reports, 2024)

Accumulation of Prion Triggers the Enhanced Glycolysis via Activation of AMKP Pathway in Prion-Infected Rodent and Cell Models - Qin Fan; Kang Xiao; Ruhan A; Li-Ping Gao; Yue-Zhang Wu; Dong-Dong Chen; Chao Hu; Xiao-Xi Jia; Chu-Mou Liu; Xin Liu; Cao Chen; Qi Shi; et al. (Molecular Neurobiology, 2024)

Engineered bispecific antibodies with enhanced breadth and potency against SARS-CoV-2 variants and SARS-related coronaviruses - Fangfang Chang; Qian Wu; Yabin Hu; Zhendong Pan; Yong-Chen Liu; Yue-Zhou Li; Mihnea Bostina; Wenpei Liu; Ping Zhao; Xiaowang Qu; Yi-Ping Li (Medical Microbiology and Immunology, 2024)

Plant Functional Traits Modulate Effects of Drought on C:N:P Stoichiometry of Plant, Litter, and Soil Microbe in an Arid Grassland - Zhaobin Song; Xiaoan Zuo; Xueyong Zhao; Xiangyun Li; Ya Hu; Jingjuan Qiao; Ping Yue; Min Chen; Shaokun Wang; Jordi Sardans; Josep Peñuelas (Journal of Soil Science and Plant Nutrition, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

A multi-perspective assessment of satellite surface Ozone products in China: Spatiotemporal variability, land cover impacts and pollution monitoring capability - Jian Wang; Yuling Du; Tianxiang Cui; Jibo Yue; Lin Sun; Haiping Si; Ping Dong; Hebing Liu; Yong Li; Lei Shi (Remote Sensing Applications: Society and Environment, 2024)

Enhanced rainfall nowcasting of tropical cyclone by an interpretable deep learning model and its application in real-time flood forecasting - Li Liu; Xiao Liang; Yue-Ping Xu; Yuxue Guo; Quan J. Wang; Haiting Gu (Journal of Hydrology, 2024)

Atomic modulation of FeN4 sites on hollow carbon nanospheres by neighboring Mn atoms for ultra-stable Zn-air batteries - Zhaowei Ji; Chenglong Qiu; Ping Li; Yifan Li; Jing Shi; Jingyi Wu; Yue Zhu; Wei Hu; Zhi Li; Huanlei Wang (Chemical Engineering Journal, 2024)

Acid-assisted pretreatment for sweet elephant grass in choline chloride/glycerol DES: Experimental and mechanism study - Yining Zhang; Weizhen Xie; Weidong Li; Yue Tang; Jiali Wu; Lihui Gan; Ling-Ping Xiao; Xu Zhang; Lu Lin; Xing Tang (Chemical Engineering Journal, 2024)

Aberrant Enhanced NLRP3 Inflammasomes and Cell Pyroptosis in the Brains of Prion-Infected Rodent Models Are Largely Associated with the Proliferative Astrocytes - Dong-Hua Zhou; Xiao-Xi Jia; Yue-Zhang Wu; Wei-Wei Zhang; Yuan Wang; Dong-Lin Liang; Li-Ping Gao; Kang Xiao; Cao Chen; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2024)

Microplastics in the human body: A comprehensive review of exposure, distribution, migration mechanisms, and toxicity - Yue Li; Liping Chen; Nonglin Zhou; Yuyuan Chen; Zhichen Ling; Ping Xiang (Science of The Total Environment, 2024)

Combating coal-burning-borne endemic arsenism in Shaanxi Province, Northwest China: The impact of high-arsenic coal ban, improved cook-stoves, and health education - Yujie Ning; Chaowei Wang; Shujin Li; Sijie Chen; Feiyu Zhang; Rong Zhou; Yuequan Yuan; Xi Lv; Yifan Wu; Yu Zhang; Zhongxue Fan; Xiaoqian Li; et al. (Journal of Hazardous Materials, 2024)

Facile fabrication of eccentric hollow molecularly imprinted polymers microspheres via miniemulsion one-step seed swelling polymerization - Zehu Wang; Xiaoliang Zhang; Zongqi Li; Guangshuo Wang; Yanming Wang; Ping Li; Xuan Yue (Journal of Environmental Chemical Engineering, 2024)

A combined experimental and theoretical study on the mechanism of catalytic oxidation of lignite to carboxylic acids by iron - Jiao-Xuan Bai; Cong Xu; Jie-Ping Wang; Rui Guo; Wei-Ze Wu; Ting Lu; Guang-Yue Li; Ying-Hua Liang (Fuel, 2024)

Exploration of hydrogen-rich gas evolution mechanism during vitrinite pyrolysis: A combined TG-MS and ReaxFF study - Yuan-Yuan Jiang; Jie-Ping Wang; Jin-Xiao Dou; Rui Guo; Li-Hua Fan; Guang-Yue Li; Ying-Hua Liang; Jiang-Long Yu (Fuel, 2024)

Study on regulation and effect mechanism of fish collagen peptide on retrogradation of corn starch gel - Yunfei Dai; Shuhan Zhang; Jinlei Li; Zhangzhang Li; Ninghua Deng; Yong Liu; Ping Wang; Dejian Huang; Yue Li (Food Bioscience, 2024)

Epidemiology and genetic diversity of bocavirus in wild rodents in urban areas of Guangzhou, Southern China - Xin-Yan Yao; Chao-Xiang Jia; Chang-Le Li; He-Ping Li; Kai Zhong; Jian-Wei Shao; Yue-Ying Wang (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Large-area and high-efficiency carbon nanotube/silicon heterojunction solar cells enabled by self-similar fiber electrodes and solid-state gel electrolytes - Xian-Gang Hu; Bingsheng Li; Yi-Ming Zhao; An-Ping Wu; Zhenhua Lin; Peng-Xiang Hou; Chang Liu; Yue Hao; Jingjing Chang (Chemical Engineering Journal, 2024)

Characterization of a glycosyltransferase from Paris polyphylla for application in biosynthesis of rare ophiopogonins and ginsenosides - Wen-Ke Xu; Chen-Xiao Zhao; Xiao-Wen Yang; Yue-Gui Chen; Li-Ping Long; Yuan-Feng Yan; Kai Guo; Sheng-Hong Li; Yan Liu (Phytochemistry, 2024)

Rapid evaluation of the quality of Smilax glabra Roxb. using QADS based on FT-NIR combined with multiple intelligent algorithms - Geng-zhi Zhan; Xin-yue Guo; Zi-chao Qiu; Lu-yao Cai; Qian Hu; Ye Gao; Shu-wan Tang; Cun-yu Li; Yun-feng Zheng; Guo-ping Peng (Food Chemistry, 2024)

Polyphenol (−)-Epigallocatechin Gallate (EGCG) mitigated kidney injury by regulating metabolic homeostasis and mitochondrial dynamics involvement with Drp1-mediated mitochondrial fission in mice - Yue-Lei Chu; Jin-Chan Pi; Yu-Fei Yao; Xuan-Ying Chen; Xiao-Ping Peng; Wen-Juan Li (Food and Chemical Toxicology, 2024)

Rapid and sensitive detection of SARS-CoV-2 based on a phage-displayed scFv antibody fusion with alkaline phosphatase and NanoLuc luciferase - Yuxue Yan; Guofu Shang; Jiling Xie; Yingying Li; Shaomei Chen; Yanqin Yu; Ping Yue; Xiaoyan Peng; Min Ai; Zuquan Hu (Analytica Chimica Acta, 2024)

Electrical structure identification of deep shale gas reservoir in complex structural area using wide field electromagnetic method - Zhi-Wen Gu; Yue-Gang Li; Chang-Heng Yu; Zhong-Ping Zou; Ai-Guo Hu; Xue-Bo Yin; Qinag Wang; Heng Ye; Zhang-Kun Tan (Applied Geophysics, 2024)

T Cells Trafficking into the Brain in Aging and Alzheimer’s Disease - Yue-Zhang Ma; Jia-Xin Cao; Yi-Shu Zhang; Xiao-Mei Su; Yu-Hong Jing; Li-Ping Gao (Journal of Neuroimmune Pharmacology, 2024)

Moss differentiating the fluxes and sources of nitrogen deposition between 1984 and 2021 in a mountain area of Northern China - Jia-Yi Li; Yu-Ping Dong; Yang Wang; Tong-Yue Deng; Zun-Tian Zhao (Chemosphere, 2024)

The impact of CYP3A4 genetic polymorphism on crizotinib metabolism and drug-drug interactions - Jing Wang; Xiao-yu Xu; Xin-yue Li; Jian-chao Luo; Zhe-yan Zhang; Jing Chen; Jian-ping Cai; Li-kang Zhang; Jian-chang Qian (Toxicology and Applied Pharmacology, 2024)

Screening and verification of outer membrane proteins of Cronobacter sakazakii with potential adhesion capability to human ileocecal adenocarcinoma cells - Chumin Zhao; Ping Li; Yufei Fan; Dongdong Zhu; Jingbo Jiao; Yue Li; Zehui Xiao; Xinjun Du; Shuo Wang (Food Bioscience, 2024)

Evolution of morphology, structure, and performance of the COF membranes with monomer concentrations: Enabling effective desalination and kinetics analysis - Li-ping Yue; Fan-xin Kong; Yi Wang; Guang-dong Sun; Ai-guo Zhou; Jin-fu Chen (Desalination, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Litoamentenes A–K, eleven undescribed cembranoids with cytotoxicity from the South China Sea soft coral Litophyton amentaceum - Yuan Zong; Jun-Jie Yang; Kai Li; Yan-Fang Pei; Hui-Yue Hou; Yue Zhang; Ci-Li Wang; Ping-Lin Li (Phytochemistry, 2024)

A versatile food packaging film fabricated by gallic acid/octanoic acid grafted chitosan: Preparation, characterization, high-efficient cells capture and photodynamic eradication of bacteria and biofilms - Ke Zhang; Lai Jiang; Ru-Kang Chen; Yu Shi; Yu-Gang Shi; Yue-Wen Chen; Rammile Ettelaie; Ping Li (Food Hydrocolloids, 2024)

Potential Plausible Role of Stem Cell for Treating Depressive Disorder: a Retrospective Review - Zhuo Chang; Qing-yi Wang; Lu-hao Li; Bei Jiang; Xue-ming Zhou; Hui Zhu; Yan-ping Sun; Xue Pan; Xu-xu Tu; Wei Wang; Chen-yue Liu; Hai-xue Kuang (Molecular Neurobiology, 2024)

Exploring the Impact of Biodegradable and Nonbiodegradable Microplastic Particles on Pb Absorption in Maize - Dan QIU; Chunmiao LU; Huarong SUN; Chaohang LI; Guangqiang LONG; Ping ZHAO; Yijun LONG; Yue DING; Cuixia SU; Zhengyan PAN; Yuefang CAO; Shuran HE (Journal of Soils and Sediments, 2024)

Dependence of evolution of Cyanobacteria superiority on temperature and nutrient use efficiency in a meso-eutrophic plateau lake - Jing Cao; Yue Wu; Ze-kun Li; Ze-ying Hou; Tian-hao Wu; Zhao-sheng Chu; Bing-hui Zheng; Ping-ping Yang; Yi-yan Yang; Cun-sheng Li; Qian-hua Li; Xia Guo (Science of The Total Environment, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

Research and application progress of microbial β-mannanases: a mini-review - Ping Wang; Xiaohui Pei; Weiqiang Zhou; Yue Zhao; Pengfei Gu; Yumei Li; Juan Gao (World Journal of Microbiology and Biotechnology, 2024)

Cell-Cycle-related Protein Centromere Protein F Deficiency Inhibits Cervical Cancer Cell Growth by Inducing Ferroptosis Via Nrf2 Inactivation - Xin hui Tang; Tian nan Zhao; Li Guo; Xin yue Liu; Wei na Zhang; Ping Zhang (Cell Biochemistry and Biophysics, 2024)
Cervical cancer (CC) is one of the severe cancers that pose a threat to women’s health and result in death. CENPF, the centromere protein F, plays a crucial role in mitosis by regulating numerous cellular processes, such as chromosome segregation during mitosis. According to bioinformatics research, CENPF serves as a master regulator that is upregulated and activated in cervical cancer. Nevertheless, the precise biological mechanism that CENPF operates in CC remains unclear. The aim of this study was to analyze the function of CENPF on cervical cancer and its mechanism. We conducted immunohistochemistry and western blot analysis to examine the expression levels of CENPF in both cervical cancer tissues and cells. To explore the hidden biological function of CENPF in cell lines derived from CC, we applied lentivirus transfection to reduce CENPF manifestation. CENPF’s main role is to regulate ferroptosis which was assessed by analyzing Reactive Oxygen Species (ROS), malonaldehyde (MDA), etc. The vitro findings were further validated through a subcutaneous tumorigenic nude mouse model. Our research finding indicates that there is an apparent upregulation of CENPF in not merely tumor tissues but also cell lines in the carcinomas of the cervix. In vitro and vivo experimental investigations have demonstrated that the suppression of CENPF can impede cellular multiplication, migration, and invasion while inducing ferroptosis. The ferroptosis induced by CENPF inhibition in cervical cancer cell lines is likely mediated through the Nrf2/HO-1 pathway. The data herein come up with the opinion that CENPF may have a crucial role in influencing anti-cervical cancer effects by inducing ferroptosis via the triggering of the Nrf2/HO-1 signaling pathway.

The effect of nitrogen input on N2O emission depends on precipitation in a temperate desert steppe - Ping Yue; Kaihui Li; Ya Hu; Jingjuan Qiao; Shaokun Wang; Xujun Ma; Tom Misselbrook; Xiaoan Zuo (Science of The Total Environment, 2024)

Binding properties of chemosensory protein 4 in Riptortus pedestris to aggregation pheromones - Jin-Bu Li; Qiang Liu; Sai Ma; Yue-Ying Wang; Xing-Zhou Liu; Chao-Wei Wang; Da-Jiang Wang; Zhuang-Zhuang Hu; Jia-Wen Gan; Xiu-Yun Zhu; Bao-Ping Li; Mao-Zhu Yin; et al. (Pesticide Biochemistry and Physiology, 2024)

Water distribution in pore systems and its influences on gas-bearing property of deep shale: A case study of the Longmaxi Formation in the Luzhou area, southern Sichuan Basin - Yue Feng; Xianming Xiao; Ping Gao; Dongfeng Hu; Ruobing Liu; Gang Li; Chengang Lu; Qin Zhou (Marine and Petroleum Geology, 2024)

A water quality assessment model involving novel fluorescence technology - Yu Hao; Yue Zhang; Bingyan Li; Huiyan Chuan; Zhaomin Wang; Jianping Shen; Zhe Chen; Ping Xie; Yong Liu (Journal of Environmental Management, 2024)

Soil physical stresses beyond the dynamic least limiting water range determine crop yields in wheat-maize system in a Vertisol - Yuekai Wang; Zhongbin Zhang; Zichun Guo; Yue Zhang; Ping Zhang; Xun Xiao; Fengmin Li; Xinhua Peng (Field Crops Research, 2024)

Bio-sorption capacity of cadmium and zinc by Pseudomonas monteilii with heavy-metal resistance isolated from the compost of pig manure - Ping Wang; Feixue Yue; Cong Shao; Qian Li; Yining Shen; Kaili Xu; Zihan Shi; Naiyu Liu; Ronghua Li; Zengqiang Zhang (Bioresource Technology, 2024)

Improved response spectrum analysis procedure for an adaptive variable friction pendulum isolated structure considering frictional dependency - Kui Yang; Ping Tan; Jiying Shang; Huating Chen; Jiaxi Li; Yue Xiang; Yafeng Li (Soil Dynamics and Earthquake Engineering, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Quercetin alleviates the toxicity of difenoconazole to the respiratory system of carp by reducing ROS accumulation and maintaining mitochondrial dynamic balance - Xiaomeng Ji; Jiajia Guo; Yeyun Ma; Shuai Zhang; Zuwang Yang; Yuanyuan Li; Kaixin Ping; Yue Xin; Zibo Dong (Toxicology and Applied Pharmacology, 2024)

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

Plant functional traits mediate the response magnitude of plant-litter-soil microbial C: N: P stoichiometry to nitrogen addition in a desert steppe - Zhaobin Song; Xiaoan Zuo; Xueyong Zhao; Jingjuan Qiao; Hu Ya; Xiangyun Li; Ping Yue; Min Chen; Shaokun Wang; Eduardo Medina-Roldán (Science of The Total Environment, 2024)

Indole alkaloids isolated from the Nicotiana tabacum-derived Aspergillus fumigatus 0338 as potential inhibitors for tobacco powdery mildew and their mode of actions - Yue-Yu Ma; Gui Pu; Hua-Yin Liu; Sui Yao; Guang-Hui Kong; Yu-Ping Wu; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Qiu-Fen Hu; Feng-Xian Yang (Pesticide Biochemistry and Physiology, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

Silybin mitigates chronic Avermectin exposure-induced intestinal damage and growth inhibition in carp - Guanglu Wang; Yue Xin; Kaixin Ping; Xuhui Xu; Ying Sun; Xing Li; Xinying Guan; Jingquan Dong (Environmental Toxicology and Pharmacology, 2024)

Pesticide avermectin-induced hepatotoxicity and growth inhibition in carp: Ameliorative capacity and potential mechanisms of quercetin as a dietary additive - Yue Xin; Xueqing Li; Kaixin Ping; Yannan Xiang; Mengxin Li; Xing Li; Haitao Yang; Jingquan Dong (Aquatic Toxicology, 2024)

Exploring the impact of urbanization on flood characteristics with the SCS-TRITON method - Hongjie Yu; Yue-Ping Xu; Hua Zhong; Yen-Ming Chiang; Li Liu (Natural Hazards, 2024)

Immunoprotective effect of silybin through blocking p53-driven caspase-9-Apaf-1-Cyt c complex formation and immune dysfunction after difenoconazole exposure in carp spleen - Enzhuang Pan; Yue Xin; Xueqing Li; Kaixin Ping; Xing Li; Ying Sun; Xuhui Xu; Jingquan Dong (Environmental Science and Pollution Research, 2024)

Metabolomics analysis to interpret changes in physiological and metabolic responses to chronic heat stress in Pekin ducks - Xiangyi-Yi Zeng; Arshad Javid; Gang Tian; Ke-Ying Zhang; Shi-Ping Bai; Xue-Mei Ding; Jian-Ping Wang; Li Lv; Yue Xuan; Shan-Shan Li; Qiu-Feng Zeng (Science of The Total Environment, 2024)

Road dust exposure and human corneal damage in a plateau high geological background provincial capital city: Spatial distribution, sources, bioaccessibility, and cytotoxicity of dust heavy metals - Zi-Yue Yang; Hai Liu; Jing-Ya Li; Ya-Bo Bao; Ji Yang; Li Li; Zi-Yu Zhao; Qin-Xiang Zheng; Ping Xiang (Science of The Total Environment, 2024)

Growing-season drought and nitrogen addition interactively impair grassland ecosystem stability by reducing species diversity, asynchrony, and stability - Peng Lv; Shanshan Sun; Yuqiang Li; Shenglong Zhao; Jing Zhang; Ya Hu; Ping Yue; Xiaoan Zuo (Science of The Total Environment, 2024)

Investigation on the failure mechanism of a tunnel entrance high-steep slope with ultra-large wedge blocks based on discrete element method - Huai-sheng Xu; Shao-jun Li; Ding-ping Xu; Xiu-yang Liu; Yue-lin Xia; Guan-qi Wang; Xing-dong Ma; Zheng-jun Zhou (Computers and Geotechnics, 2024)

Self-powered photocatalytic system fabricated by bifunctional coordination polymers - Qiang Zhang; Chao Huang; Yue Zhang; Saiwei Liu; Dianbo Zhang; Ping Li; Fei Wang; Dandan Wang; Ying-Ying Zhang (Chemical Engineering Journal, 2024)

Histone methyltransferase KMT2D inhibits ENKTL carcinogenesis by epigenetically activating SGK1 and SOCS1 - Yue-Hua Zhang; Qing Tao; Wen-Yan Zhang; Sha Zhao; Wei-Ping Liu; Li-Min Gao (Genes & Genomics, 2024)

A pair of new chromone enantiomers from Xylaria nigripes - Jing Li; Yue-Ping Jiang; Lan-Qing Li; Hong-Ping Long; Hai-Tao Liu; Rong Yang; Shao Liu; Wen-Xuan Wang; Ji-Kai Liu (Natural Product Research, 2024)

MiRNAs enabled Golden pompano (Trachinotus blochii) in response to different reoxygenation patterns after hypoxic stress - Tian Jiang; Jun Long Sun; Chun Xiu Jin; Yu Zhang; Zai Hui Tong; Yue Gu; Fu Cheng Yao; Li Ping Shi; Fei Biao Song; Jian Luo (Aquaculture, 2024)

Plant composition change mediates climate drought, nitrogen addition, and grazing effects on soil net nitrogen mineralization in a semi-arid grassland in North China - Peng Lv; Shanshan Sun; Yuqiang Li; Shenglong Zhao; Jing Zhang; Ya Hu; Ping Yue; Xiaoan Zuo (Science of The Total Environment, 2024)

Drought intensity and post-drought precipitation determine vegetation recovery in a desert steppe in Inner Mongolia, China - Xiangyun Li; Zhaobin Song; Ya Hu; Jingjuan Qiao; Yuheng Chen; Shaokun Wang; Ping Yue; Min Chen; Yuguang Ke; Chong Xu; Qiang Yu; Xiaoan Zuo (Science of The Total Environment, 2024)

Analyzing sulfur cycle process in natural lakes based on the combination of sulfur-producing genes and fluorescence technology - Jianping Shen; Changhui Zhang; Jing Li; Yue Zhang; Yu Hao; Ping Xie; Zhe Chen; Yong Liu (Journal of Cleaner Production, 2024)

Accumulation of livestock manure–derived heavy metals in the Hexi Corridor oasis agricultural alkaline soil and bioavailability to Chinese cabbage (Brassica pekinensis L.) after 4-year continuous application - Tian-Xia Guan; Zhao-Ping Lu; Ming Yue; Bao-Guo Li; Ai-Gen Fu; Xu-Dong Zhang; Zhong-Hu Li (Environmental Pollution, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Chronic cadmium exposure triggered ferroptosis by perturbing the STEAP3-mediated glutathione redox balance linked to altered metabolomic signatures in humans - Ping Deng; Jingdian Li; Yonghui Lu; Rongrong Hao; Mindi He; Min Li; Miduo Tan; Peng Gao; Liting Wang; Huihui Hong; Jiawen Tao; Muxue Lu; et al. (Science of The Total Environment, 2023)

Identification and characterization of a novel Iflavirus in a stored-product psocid, Liposcelis bostrychophila (Psocodea: Liposcelididae) - Peng-Yu Guo; Dan-Dan Wei; Hua-Yue Feng; Xin-Ping Tang; Yu-Ang Chen; Yi Li; Jin-Jun Wang (Journal of Stored Products Research, 2023)

Investigation of the impact mechanisms and patterns of meteorological factors on air quality and atmospheric pollutant concentrations during extreme weather events in Zhengzhou city, Henan Province - Jinmian Ni; Yue Zhao; Bin Li; Jianhua Liu; Yinling Zhou; Ping Zhang; Jin Shao; Yanfei Chen; Jiming Jin; Chao He (Atmospheric Pollution Research, 2023)

Transposon-based identification of genes involved in the rimocidin biosynthesis in Streptomyces rimosus M527 - Hai-yue Bao; Hui-jie Li; Yong-yong Zhang; Andreas Bechthold; Xiao-ping Yu; Zheng Ma (World Journal of Microbiology and Biotechnology, 2023)

Establishment and characterization of a novel hilar cholangiocarcinoma cell line, CBC3T-1 - Mingzhen Bai; Ningzu Jiang; Wenkang Fu; Chongfei Huang; Liang Tian; Ningning Mi; Long Gao; Haidong Ma; Yawen Lu; Jie Cao; Chao Zhang; Ping Yue; et al. (Human Cell, 2023)
Cholangiocarcinoma (CCA) is a group of malignant heterogeneous cancer arising from the biliary tree. The tumor is characterized by insidious onset, high degree of malignancy, poor prognosis, and high recurrence rate. Immortalized cancer cell lines are the best and easiest models for in vitro cancer research. Here, we established a naturally immortalized highly tumorigenic hilar cholangiocarcinoma (hCCA) cell line, CBC3T-1. The CBC3T-1 cell line was cultured for over 60 passages. Thorough analysis showed that CBC3T-1 cells share characteristics similar to original tumor cells from patients with cholangiocarcinoma and display a stable phenotype, including features of epithelial origin, stem cell-like properties, as well as a high invasive and migratory capability and tumorigenicity in mice. Furthermore, this cell line showed the best sensitivity to paclitaxel, followed by gemcitabine. RNA sequencing and whole‑exome sequencing showed that cancer-associated pathways and somatic mutations played a dominant role in the development of CCA. We established and characterized a new hCCA cell line, CBC3T-1, which contributes to a better understanding of bile duct cancer, and can be used to study tumorigenesis and progression and the role of anticancer drugs.

Biomass-derived carbon dots with light conversion and nutrient provisioning capabilities facilitate plant photosynthesis - Bingxu Cheng; Zhilin Yang; Feiran Chen; Le Yue; Xuesong Cao; Jing Li; Hai-Long Qian; Xiu-Ping Yan; Chuanxi Wang; Zhenyu Wang (Science of The Total Environment, 2023)

Environmental cadmium exposure facilitates mammary tumorigenesis via reprogramming gut microbiota-mediated glutamine metabolism in MMTV-Erbb2 mice - Yang Yue; Huadong Zhang; Ping Deng; Miduo Tan; Chengzhi Chen; Bo Tang; Jingdian Li; Fengqiong Chen; Qi Zhao; Ling Li; Rongrong Hao; Hui Wang; et al. (Science of The Total Environment, 2023)

Extraction and characterization of anti-virus anthraquinones from Nicotiana tabacum-derived Aspergillus oryzae YNCA1220 - Feng-Xian Yang; Yue-Yu Ma; Yu-Ping Wu; Gao-Kun Zhao; Yong-Ping Li; Zhen-Jie Li; Xue-Mei Li; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Guang-Hui Kong; Qiu-Fen Hu (Pesticide Biochemistry and Physiology, 2023)

Non-enzymatic browning of wine induced by monomeric flavan-3-ols: A review - Xu Zhao; Chang-Qing Duan; Si-Yu Li; Xin-Ke Zhang; Hong-Yue Zhai; Fei He; Yu-Ping Zhao (Food Chemistry, 2023)

Abamectin induced brain and liver toxicity in carp: The healing potential of silybin and potential molecular mechanisms - Xinyu Wu; Yue Xin; Yeyun Ma; Kaixin Ping; Qiulu Li; Ying Sun; Zunhan Hu; Jingquan Dong (Fish & Shellfish Immunology, 2023)

Changed mercury speciation in clouds driven by changing cloud water chemistry and impacts on photoreduction: Field evidence at Mt. Tai in eastern China - Jiebo Zhen; Tao Li; Xinmiao Xu; Ping Du; Yue Song; Xiaoling Nie; Xinghui Liu; Hengde Liu; Yujian Bi; Xinfeng Wang; Likun Xue; Yan Wang (Water Research, 2023)

Effects of interspecific interactions on soil carbon emission and efficiency in the semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Shuang-Guo Zhu; Hong-Yan Tao; Aziz Khan; Aimee Grace Uzamurera; Bao-Zhong Wang; Jun-Ming Jin; Yue Ma; Wen-Bo Li; Xiu-Ping Tao; et al. (Soil and Tillage Research, 2023)

Sodium alginate based energy harvesting fibers: Multiscale structure and moist-electrical properties - Rui Zhang; Hai Wang; Meijie Qu; Shuhui Li; Yue Ma; Xinye Li; Ping Tang; Yuezhen Bin (Chemical Engineering Journal, 2023)

Multi-trait functional diversity predicts ecosystem multifunctionality under nitrogen addition in a desert steppe - Ya Hu; Aixia Guo; Xiangyun Li; Ping Yue; Shenglong Zhao; Peng Lv; Xiaoan Zuo (Plant and Soil, 2023)

Construction of covalent organic framework nanozymes with photo-enhanced hydrolase activities for colorimetric sensing of organophosphorus nerve agents - Sai-Jin Xiao; Ming-Yue Yuan; Ya-Di Shi; Meng-Ping Wang; Hui-Han Li; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Comprehensive understanding of tetracycline hydrochloride adsorption mechanism onto biochar-based gel pellets based on the combination of characterization-based and approximate site energy distribution methods - Bai-Qin Zhou; Qian-Qian Sang; Yu-Jun Wang; Hui Huang; Fang-Jun Wang; Rui-Chun Yang; Yuan-Tian Zhao; Zi-Jie Xiao; Chun-Yue Zhang; Hui-Ping Li (Journal of Cleaner Production, 2023)

Numeric and nonnumeric information input to predict adsorption amount, capacity and kinetics of tetracyclines by biochar via machine learning - Bai-Qin Zhou; Rui-Chun Yang; Hui-Ping LI; Yu-Jun Wang; Chun-Yue Zhang; Zi-Jie Xiao; Zhong-Qi He; Wei-Hai Pang (Chemical Engineering Journal, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Enzymatic activity of 38 CYP2C9 genotypes on ibuprofen - Ling-jing Yuan; Xiang-yu Li; Feng Ye; Xin-yue Li; Qing-qing Li; Yun-shan Zhong; Shi-yu Wang; Ya-hui Wang; Guo-xin Hu; Jian-ping Cai; Jun-wei Li (Food and Chemical Toxicology, 2023)

Transcriptomics integrated with metabolomics unravels the interweaving of inflammatory response and 1-stearoyl-2-arachidonoyl-sn-glycerol metabolic disorder in chronic cadmium exposure-induced hepatotoxicity - Rongrong Hao; Heng Xiao; Hui Wang; Ping Deng; Yang Yue; Jingdian Li; Yan Luo; Li Tian; Jia Xie; Mengyan Chen; Zhou Zhou; Fengqiong Chen; et al. (Environmental Toxicology and Pharmacology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Fluorescence enhancement of surface plasmon coupled emission by Au nanobipyramids and its modulation effect on multi-wavelength radiation - Kai-Xin Xie; Rui-Ping Huo; Xiu-Li Song; Qiao-Ling Liu; Yue Jiang; Yu-Han Li; Lu-Lu Dong; Jia-Xin Cheng (Analytica Chimica Acta, 2023)

Long-term hypoxia and reoxygenation induced oxidative stress lead to immunosuppression and apoptosis in golden pompano (Trachinotus blochii) - Yue Gu; Jun Long Sun; Fu Cheng Yao; Tian Jiang; Chun Xiu Jin; Li Ping Shi; Shu Kui Sun; Fei Biao Song; Jian Luo (Frontiers in Marine Science, 2023)
The fluctuations of dissolved oxygen (DO) often lead to hypoxia in aquaculture, which has a huge adverse impact on fish. This study mainly investigated the effects of long-term hypoxia on oxidative stress, immune response, and cell apoptosis in the liver of golden pompano ( Trachinotus blochii ), which is not tolerant to hypoxia. So we conducted a 14 day low oxygen stress experiment on the golden pompano with a DO of 3.0 ± 0.2 mg/L, then restore the DO to normal levels and continue the 14 day reoxygenation experiment. Results showed that hypoxia and reoxygenation led to significant changes in liver structure. During hypoxia and reoxygenation, the expression of oxidative stress related genes ( SOD1 , SOD2 , GSH-Px , and CAT ) and levels of antioxidant enzymes (CAT and MDA) in the liver were increased. Liver lysozyme activity and the relative expression of the pro-inflammatory factors interleukin ( IL)-1β were significantly increased, but the expression of IL-34 was down-regulated during hypoxia. The expression of IL-12β was significantly increased during reoxygenation. The expression of anti-inflammatory factor IL -11 was decreased duringreoxygenation. The expression of toll like receptors ( TLRs ) -7, -8, and -9 increases after hypoxia and decreases after reoxygenation, indicating that both hypoxia and reoxygenation affect the immune response. In addition, during hypoxia and reoxygenation, TUNEL-positive signals increased, the bcl2/bax ratio decreased, the expression levels of caspases-3 and -8 were significantly up-regulated during hypoxia, and expression levels of caspases-9 was up-regulated during reoxygenation. In summary, hypoxia and reoxygenation can cause oxidative stress, induce inflammatory reactions, inhibit immune processes, activate apoptosis, and lead to liver damage of the golden pompano, which may be irreversible.

A comprehensive SERS, SEM and EDX study of individual atmospheric PM2.5 particles in Chengdu, China - Dongxian Li; Weisheng Yue; Tiancheng Gong; Ping Gao; Tao Zhang; Yunfei Luo; Changtao Wang (Science of The Total Environment, 2023)

Combined effect of surface PM2.5 assimilation and aerosol-radiation interaction on winter severe haze prediction in central and eastern China - Yue Peng; Hong Wang; Xiaoye Zhang; Ping Wang; Siting Li; Zhaodong Liu; Wenjie Zhang; Huizheng Che (Atmospheric Pollution Research, 2023)

Fluorescence Properties and Chemical Composition of Fine Particles in the Background Atmosphere of North China - Ping Li; Siyao Yue; Xiaoyang Yang; Di Liu; Qiang Zhang; Wei Hu; Shengjie Hou; Wanyu Zhao; Hong Ren; Gang Li; Yuanguan Gao; Junjun Deng; et al. (Advances in Atmospheric Sciences, 2023)

The spatial distribution, health risk, and cytotoxicity of metal(loid)s in contaminated field soils: The role of Cd in human gastric cells damage - Jiao-Yang Ma; Wei-Yu Li; Zi-Yue Yang; Jin-Zhou Su; Li Li; Yi-Rong Deng; Yun-Fei Tuo; You-Ya Niu; Ping Xiang (Science of The Total Environment, 2023)

Neuroprotective methylsuccinic acid and enoic acid derivatives from the fungus Xylaria longipes - Jing Li; Yu-Fen Tan; Si-Qian Zhou; Shao Liu; Wen-Xuan Wang; Yue-Ping Jiang; Hong-Ping Long; Ji-Kai Liu (Phytochemistry, 2023)

Transcriptomic and physiological analysis of the effect of octanoic acid on Meloidogyne incognita - Jian-Yu Wang; Qiu-Yue Li; Li Ren; Cheng Guo; Jian-Ping Qu; Zheng Gao; Hui-Fang Wang; Qian Zhang; Bo Zhou (Pesticide Biochemistry and Physiology, 2023)

Three new isoquinoline alkaloids from the cigar tobacco-derived endophytic fungus Aspergillus felis - Yue-Yu Ma; Gui Pu; Xue-Ju Cha; Rui-Feng Xiong; Guang-Hai Zhang; Heng Yao; Mei-Fen Bao; Guang-Hui Kong; Yin-Ke Li; Qiu-Fen Hu; Yu-Ping Wu (Phytochemistry Letters, 2023)

The roles of red mud as desulfurization and denitrification in flue gas: A review - Shuai Liu; Zewei Liu; Hengxi Zhu; Zixuan Wang; Junjiang Guo; Xiaoyue Zhang; Hongxin Yu; Xiangdong Yue; Ping Ning; Bin Li (Journal of Environmental Chemical Engineering, 2023)

Rapid granulation of aerobic granular sludge in an integrated moving bed biofilm reactor-membrane bioreactor: Effects and mechanism of Streptomyces cellulosus microspheres - Huanlong Zhang; Yue Xu; Liying Bin; Ping Li; Fenglian Fu; Shaosong Huang; Bing Tang (Bioresource Technology Reports, 2023)

Effects of Bacillus subtilis BS-Z15 on Intestinal Microbiota Structure and Body Weight Gain in Mice - Jun Yang; Huan-Chen Ning; Qi Zhang; Jun-Qi Yue; Xi-Yuan Cao; Jin-Yu Li; Ling Liu; He-Ping Zhao; Hui-Xin Zhao (Probiotics and Antimicrobial Proteins, 2023)

High nitrogen addition induces functional trait divergence of plant community in a temperate desert steppe - Jingjuan Qiao; Xiaoan Zuo; Ping Yue; Shaokun Wang; Ya Hu; Xinxin Guo; Xiangyun Li; Peng Lv; Aixia Guo; Shanshan Sun (Plant and Soil, 2023)

Fermented foods and metabolic outcomes in diabetes and prediabetes: A systematic review and meta-analysis of randomized controlled trials - Xiao-Feng Zhang; Yue Qi; Yong-Ping Zhang; Jin-Lan Deng; Xiao-Li Chen; Ruo-Nan Li; Qi-Lun Zhou; Jian-Ming Fan (Critical Reviews in Food Science and Nutrition, 2023)

Restoration of sedimentary environment and geochemical features of deep marine Longmaxi shale and its significance for shale gas: A case study of the Dingshan area in the Sichuan Basin, South China - Yue Feng; Xianming Xiao; Ping Gao; Enze Wang; Dongfeng Hu; Ruobing Liu; Gang Li; Chengang Lu (Marine and Petroleum Geology, 2023)

Responses of net ecosystem carbon budget and net global warming potential to long-term nitrogen deposition in a temperate grassland - Si Chen; Ping Yue; Tianxiang Hao; Kaihui Li; Tom Misselbrook; Xuejun Liu (CATENA, 2023)

Extracellular Vesicles Derived from Bone Mesenchymal Stem Cells Carrying circ_0000075 Relieves Cerebral Ischemic Injury by Competitively Inhibiting miR-218-5p and Up-regulating E3 Ubiquitin Ligase SMURF2 - Yue Liu; You-Ping Li; Li-Min Xiao; Li-Ke Chen; Su-Yue Zheng; Er-Ming Zeng; Chun-Hua Xu (Molecular Neurobiology, 2023)

The effect of episodic foresight on intertemporal decision-making: the role of future self-continuity and perceived control - Hong-Yue Sun; Yuan-Ping Jiang; Xin Wang; Li-Ying Cui; Hong-Mei Sun (Cognitive Processing, 2023)

Effects of polyethylene and biodegradable microplastics on photosynthesis, antioxidant defense systems, and arsenic accumulation in maize (Zea mays L.) seedlings grown in arsenic-contaminated soils - Huarong Sun; Yilan Shi; Ping Zhao; Guangqiang Long; Chaohang Li; Jiajing Wang; Dan Qiu; Chunmiao Lu; Yue Ding; Lin Liu; Shuran He (Science of The Total Environment, 2023)

Undescribed phloroglucinol derivatives with antiviral activities from Dryopteris atrata (Wall. Ex Kunze) Ching - Ji-hui Zhang; Jin-lin Chen; Wei-bin Xu; Yi-ping Xia; Hao-yue Zhu; Jing-hao Wang; Yao-lan Li; Guo-cai Wang; Yu-bo Zhang; Neng-hua Chen (Phytochemistry, 2023)

Single-cell transcriptomic analysis reveals the developmental trajectory and transcriptional regulatory networks of pigment glands in Gossypium bickii - Yue Sun; Yifei Han; Kuang Sheng; Ping Yang; Yuefen Cao; Huazu Li; Qian-Hao Zhu; Jinhong Chen; Shuijin Zhu; Tianlun Zhao (Molecular Plant, 2023)

Comparison of two commercial methods with a UHPLC–MS/MS method for the determination of multiple mycotoxins in cereals - Ying-yue Zhang; Mei-juan Zhao; Chun-yao Liu; Kai Ma; Tian-yu Liu; Fei Chen; Li-na Wu; De-jun Hu; Guang-ping Lv (Food Chemistry, 2023)

Silk fibroin-based colorimetric microneedle patch for rapid detection of spoilage in packaged salmon samples - Jiang-Yue Wang; Li-Jian Chen; Xu Zhao; Xiu-Ping Yan (Food Chemistry, 2023)

Insights into the shift of microbial community related to nitrogen cycle, especially N2O in vanadium-polluted soil - Xuna Liu; Lina Pang; Yao Yue; Hongna Li; Efthalia Chatzisymeon; Yuanyuan Lu; Ping Yang (Environmental Pollution, 2023)

Eicosane-based thermo-conductive phase change composite for efficient capture solar energy and using in real-environment as power source - Linhong Li; Maohua Li; Yue Qin; Yapeng Chen; Wen Dai; Zhenbang Zhang; Xiangdong Kong; Ping Gong; Yandong Wang; Rongjie Yang; Bo Wang; Tao Cai; et al. (Chemical Engineering Journal, 2023)

Theoretical insight into the competitive effect of CO2 and additive H2O in coke gasification - Lei Liang; Zhang Sun; Hang Zhang; Hao-Dong Liu; Jie-Ping Wang; Guang-Yue Li; Ying-Hua Liang (Chemical Engineering Journal, 2023)

Initial water rights allocation of Industry in the Yellow River basin driven by high-quality development - Xiang-nan Chen; Fang Li; Feng-ping Wu; Xia Xu; Yue Zhao (Ecological Modelling, 2023)

Effects of altered precipitation patterns on soil nitrogen transformation in different landscape types during the growing season in northern China - Peng Lv; Shanshan Sun; Xueyong Zhao; Yuqiang Li; Shenglong Zhao; Jing Zhang; Ya Hu; Aixia Guo; Ping Yue; Xiaoan Zuo (CATENA, 2023)

Gas-in-place and its influence factors of the upper Paleozoic coal-bearing shale in the Qinshui Basin, China - Chengang Lu; Ping Gao; Gang Li; Yue Feng; Xiaorong Qu; Yufei Su; Xianming Xiao (Frontiers of Earth Science, 2023)

Contrasting relationships between plant-soil microbial diversity are driven by geographic and experimental precipitation changes - Xiaoan Zuo; Shanshan Sun; Shaokun Wang; Ping Yue; Ya Hu; Shengnlong Zhao; Xinxin Guo; Xiangyun Li; Min Chen; Xujun Ma; Hao Qu; Weigang Hu; et al. (Science of The Total Environment, 2023)

Long-term cadmium exposure impairs cognitive function by activating lnc-Gm10532/m6A/FIS1 axis-mediated mitochondrial fission and dysfunction - Ping Deng; Huadong Zhang; Liting Wang; Sheng Jie; Qi Zhao; Fengqiong Chen; Yang Yue; Hui Wang; Li Tian; Jia Xie; Mengyan Chen; Yan Luo; et al. (Science of The Total Environment, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Fluorescent imaging to provide visualized evidences for mercury induced hypoxia stress - Li Zhang; Liangwei Zhang; Xia Zhang; Ping Liu; Yue Wang; Xiaoyue Han; Lingxin Chen (Journal of Hazardous Materials, 2023)

Effects of multi-resource addition on grassland plant productivity and biodiversity along a resource gradient - Xinxin Guo; Xiaoan Zuo; Eduardo Medina-Roldán; Aixia Guo; Ping Yue; Xueyong Zhao; Jingjuan Qiao; Xiangyun Li; Min Chen; Cunzheng Wei; Tian Yang; Yuguang Ke; et al. (Science of The Total Environment, 2023)

Sedimentary dinoflagellate cyst records of human-induced environmental changes in Daya Bay, the northern South China Sea - Ping-Ping Shen; Ying Li; Ya-Nan Tang; Qing-Shang Song; Yue Xue (Journal of Marine Systems, 2023)

3-MCPD exposure enhances ovarian fibrosis and reduces oocyte quality in mice - Quan-Kuo He; Yan-Ping Li; Zhi-Ran Xu; Wen-Bo Wei; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Yan-Zhu Chen; Hai-Long Wang; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2023)

Study on axial compression performance of double steel plate-concrete composite walls with stiffening ribs and tie plates - Yue Yang; Bin Wu; Yang-Ping Yao; Li-Yan Xu; Dong Zhang; Song-Han Wang (Engineering Structures, 2023)

Dysfunction of DNA repair for boosted tumor cell cycle arrest based on NIR-II biodegradable Te-prussian blue nanorod - Xiaoyang Liang; Ping Liu; Wen Li; Long Binh Vong; Tingting Wang; Lujing Geng; Yue Zhou; Siyu Wang; Qiang Lu; Fengping Tan; Xinxing Wang; Nan Li (Chemical Engineering Journal, 2023)

Photo-rechargeable all-solid-state lithium − sulfur batteries based on perovskite indoor photovoltaic modules - Tian-Tian Li; Yuan-Bo Yang; Bo-Sheng Zhao; Yue Wu; Xiao-Wen Wu; Peng Chen; Xue-Ping Gao (Chemical Engineering Journal, 2023)

Ten years of warming increased plant-derived carbon accumulation in an East Asian monsoon forest - Jing Zhang; Luhui Kuang; Zhijian Mou; Toshiaki Kondo; Jun Koarashi; Mariko Atarashi-Andoh; Yue Li; Xuli Tang; Ying-Ping Wang; Josep Peñuelas; Jordi Sardans; Dafeng Hui; et al. (Plant and Soil, 2022)

A Fundamental Role of Slope Aspect and Elevation in Controlling Diversity Patterns of Soil Bacterial Communities: Insights from an Arid-Montane Ecosystem in China - Long-Fei Chen; Jun-Qia Kong; Zhi-Bin He; Wen-Zhi Zhao; Ming-Dan Song; Yue-Mei Li; Yuan Gao; Shu-Ping Yang (Journal of Soil Science and Plant Nutrition, 2022)

Extreme drought does not alter the stability of aboveground net primary productivity but decreases the stability of belowground net primary productivity in a desert steppe of northern China - Xiangyun Li; Xiaoan Zuo; Xueyong Zhao; Shaokun Wang; Ping Yue; Chong Xu; Qiang Yu; Eduardo Medina-Roldán (Environmental Science and Pollution Research, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Stem Cell-Derived Exosomes: A New Method for Reversing Skin Aging - Jin-Yan Wu; Sai-Nan Wu; Li-Ping Zhang; Xian-Sheng Zhao; Yue Li; Qu-Yang Yang; Ruo-Yue Yuan; Jian-Lan Liu; Hong-Ju Mao; Ning-Wen Zhu (Tissue Engineering and Regenerative Medicine, 2022)

Depletion of serum-derived exosomes aggravates heat stress-induced damage of bovine mammary epithelial cells - Yue Wang; Hui-Li Wang; Zhi-Ping Lin; Ji-Feng Zhong; Kun-Lin Chen; Xing Duan (Molecular Biology Reports, 2022)

Enhanced M-CSF/CSF1R Signaling Closely Associates with PrPSc Accumulation in the Scrapie-Infected Cell Line and the Brains of Scrapie-Infected Experimental Rodents - Ying Xia; Cao Chen; Jia Chen; Chao Hu; Wei Yang; Lin Wang; Lian Liu; Li-Ping Gao; Yue-Zhang Wu; Dong-Dong Chen; Qi Shi; Zhi-Bao Chen; et al. (Molecular Neurobiology, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Evaluating the performance of hydrological models with joint multifractal spectra - Zhixu Bai; Yue-Ping Xu; Suli Pan; Li Liu; Zixia Wang (Hydrological Sciences Journal, 2022)

Transport process and mechanism of the Hongshiyan rock avalanche triggered by the 2014 Ludian earthquake, China - Shi-lin Zhang; Yue-ping Yin; Hai-bo Li; Wen-pei Wang; Jia-wen Zhou (Landslides, 2022)

The Role of Post-Translational Modifications on the Structure and Function of Tau Protein - Haiqiong Ye; Yue Han; Ping Li; Zhengding Su; Yongqi Huang (Journal of Molecular Neuroscience, 2022)

Expanding the clinical spectrum of adult-onset neuronal intranuclear inclusion disease - Yuwen Cao; Jingying Wu; Yunhua Yue; Chao Zhang; Shihua Liu; Ping Zhong; Shige Wang; Xiaojun Huang; Weiping Deng; Jing Pan; Lan Zheng; Qing Liu; et al. (Acta Neurologica Belgica, 2022)

Citrus flavonoids and their antioxidant evaluation - Yue Wang; Xiao-Juan Liu; Jie-Biao Chen; Jin-Ping Cao; Xian Li; Chong-De Sun (Critical Reviews in Food Science and Nutrition, 2022)

Transcriptomic analyses reveal the effect of nitric oxide on the lateral root development and growth of mangrove plant Kandelia obovata - Ming-Yue Wei; Huan Li; You-Hui Zhong; Zhi-Jun Shen; Dong-Na Ma; Chang-Hao Gao; Yi-Ling Liu; Wen-Hua Wang; Jing-Ya Zhang; Yan-Ping You; Hai-Lei Zheng (Plant and Soil, 2022)

Direct and indirect effects of precipitation change and nutrients addition on desert steppe productivity in Inner Mongolia, northern China - Xinxin Guo; Xiaoan Zuo; Ping Yue; Xiangyun Li; Ya Hu; Min Chen; Qiang Yu (Plant and Soil, 2022)

Effects of temperature, moisture, substrates and soil coverage on sclerotium germination and hyphal growth of Southern blight of apple in China - Xiang-li Dong; Chang-yan Gao; Ping-liang Li; Sen Lian; Shan-yue Zhou; Bao-hua Li (European Journal of Plant Pathology, 2022)

Aberrant functional and effective connectivity of the frontostriatal network in unilateral acute tinnitus patients with hearing loss - Gang-Ping Zhou; Yu-Chen Chen; Wang-Wei Li; Heng-Le Wei; Yu-Sheng Yu; Qing-Qing Zhou; Xindao Yin; Yue-Jin Tao; Hong Zhang (Brain Imaging and Behavior, 2022)

Estimating the added value of GRACE total water storage and uncertainty quantification in seasonal streamflow forecasting - Li Liu; Jingkai Xie; Haiting Gu; Yue-Ping Xu (Hydrological Sciences Journal, 2022)

Characterisation of teaghrelin-like principles from Assam tea cultivated in Thailand - Yue-Chiun Li; Chutima Tanapichatsakul; Patcharee Pripdeevech; Tsong Long Hwang; Ping-Chung Kuo; Jason T. C. Tzen (Natural Product Research, 2022)

Scalp Acupuncture Protects Against Neuronal Ferroptosis by Activating The p62-Keap1-Nrf2 Pathway in Rat Models of Intracranial Haemorrhage - Ming-Yue Li; Xiao-Hong Dai; Xue-Ping Yu; Wei Zou; Wei Teng; Peng Liu; Xin-Yang Yu; Qi An; Xin Wen (Journal of Molecular Neuroscience, 2022)
Intracerebral haemorrhage (ICH) can be a catastrophic event; even if the initial stages of the pathology were well-managed, a number of patients experience varied residual neurological deficits following the insult. Ferroptosis is a recently identified type of cell demise which is tightly linked to the neurological impairment associated with ICH. In the current work, the prophylactic impact of scalp acupuncture (SA) therapy on autologous blood injection murine models of ICH was investigated in order to establish whether SA could mitigate the secondary damage arising following ICH by moderating ferroptosis. The pathophysiological mechanisms associated with this process were also explored. Ludmila Belayev tests were utilised for the characterisation of neurological damage. Haematoxylin–eosin staining was employed in order to determine the cerebral impact of the induced ICH. Malondialdehyde (MDA) and iron titres in peri-haemorrhagic cerebral tissues were appraised using purchased assay kits. Transmission electron microscopy delineated mitochondrial appearances within nerve cell bodies from the area of haemorrhage. Western blotting techniques were utilised to assay the degree of protein expression of NeuN, sequestosome 1 (p62), nuclear factor erythroid 2-related factor 2 (Nrf2), Kelch-like ECH-associated protein 1 (Keap1), glutathione peroxidase 4 (GPX4) and ferritin heavy chain 1 (FTH1). The frequencies of Nrf2, GPX4 and FTH1 positive cells, respectively, were documented with immunohistochemical staining. The results demonstrated that therapy with SA after ICH mitigated MDA and iron sequestration, diminished the appearance of contracted mitochondria with increased outer mitochondrial membrane diameter within the nerve cell bodies, and suppressed neuronal ferroptosis. The pathways responsible for these effects may encompass amplified p62, Nrf2, GPX4 and FTH1 expression, together with decreased Keap1 expression. Application of SA reduced identified neurobehavioural abnormalities after ICH; no disparities were observed between the consequences of SA therapy and deferoxamine delivery. It can be surmised that intervention with SA enhanced recovery after ICH by triggering the antioxidant pathway, p62/Keap1/Nrf2, and causing FTH1 and GPX4 upregulation, factors that participate in diminishing excess iron and thus in mitigating lipid peroxidation insults arising from ferroptosis following ICH.

Responses of ecosystem respiration, methane uptake and nitrous oxide emission to drought in a temperate desert steppe - Ping Yue; Xiaoan Zuo; Kaihui Li; Xiangyun Li; Shaokun Wang; Xujun Ma; Hao Qu; Min Chen; Liangxu Liu; Tom Misselbrook; Qiang Yu (Plant and Soil, 2021)

External evaluation of published population pharmacokinetic models of polymyxin B - Ya-qian Li; Kai-feng Chen; Jun-jie Ding; Hong-yi Tan; Nan Yang; Ya-qi Lin; Cui-fang Wu; Yue-liang Xie; Guo-ping Yang; Jing-Jing Liu; Qi Pei (European Journal of Clinical Pharmacology, 2021)

Astaxanthin Ameliorates Blood Pressure in Salt-Induced Prehypertensive Rats Through ROS/MAPK/NF-κB Pathways in the Hypothalamic Paraventricular Nucleus - Hong-Li Gao; Xiao-Jing Yu; Yan Zhang; Chen-Long Wang; Yi-Ming Lei; Jia-Yue Yu; Dong-Miao Zong; Kai-Li Liu; Dong-Dong Zhang; Ying Li; Hua Tian; Nian-Ping Zhang; et al. (Cardiovascular Toxicology, 2021)

Genetic Prion Disease: Insight from the Features and Experience of China National Surveillance for Creutzfeldt-Jakob Disease - Qi Shi; Cao Chen; Kang Xiao; Wei Zhou; Li-Ping Gao; Dong-Dong Chen; Yue-Zhang Wu; Yuan Wang; Chao Hu; Chen Gao; Xiao-Ping Dong (Neuroscience Bulletin, 2021)

Geo-structures and deformation-failure characteristics of rockslide areas near the Baige landslide scar in the Jinsha River tectonic suture zone - Shi-lin Zhang; Yue-ping Yin; Xie-wen Hu; Wen-pei Wang; Zong-liang Li; Xin-ming Wu; Gang Luo; Sai-nan Zhu (Landslides, 2021)

Emerging role of air pollution in chronic kidney disease - Yue Chen; Fan Cao; Jian-Ping Xiao; Xin-Yu Fang; Xue-Rong Wang; Li-Hong Ding; De-Guang Wang; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

A comparative study of peroxydisulfate and peroxymonosulfate activation by a transition metal–H2O2 system - Yanli Zhu; Yuan Liu; Ping Li; Yue Zhang; Gang Wang; Youxian Zhang (Environmental Science and Pollution Research, 2021)

Metabolic cold adaptation in the Asiatic toad: intraspecific comparison along an altitudinal gradient - Song Tan; Ping Li; Zhongyi Yao; Gaohui Liu; Bisong Yue; Jinzhong Fu; Jingfeng Chen (Journal of Comparative Physiology B, 2021)

Steroidal glycosides from the underground parts of Hosta ventricosa and their anti-inflammatory activities in mice - Hong-Biao Chu; Nan-Nan Li; Zong-Ping Zhang; Xiao-Yue Hu; Cai-Yun Yu; Lei Hua (Natural Product Research, 2021)

Influence of major water conservation projects on river channels and shorelines in the middle and lower reaches of the Yangtze River - Yue-hua Jiang; He-qin Cheng; Quan-ping Zhou; Yun Li; Guo-qiang Yang; Yang Jin; Shi-jia Mei; Xuan Gu; Hong Zhang (Arabian Journal of Geosciences, 2021)

Fine mapping QTL and mining genes for protein content in soybean by the combination of linkage and association analysis - Xiyu Li; Ping Wang; Kaixin Zhang; Shulin Liu; Zhongying Qi; Yanlong Fang; Yue Wang; Xiaocui Tian; Jie Song; Jiajing Wang; Chang Yang; Xu Sun; et al. (Theoretical and Applied Genetics, 2021)

Numerical modeling of bed deposition in rapid flow-like landslides: a case study of the Gaolou landslide in Shaanxi Province, China - Wei Shen; Tong-lu Li; Matteo Berti; Ping Li; Yu-lu Lei; Yue-qiang Shen (Journal of Mountain Science, 2021)

Differential response of microbial diversity and abundance to hydrological residual time and age in cascade reservoirs - Yihong Yue; Fushun Wang; Zhiwei Fu; Yi Tang; Jing Ma; Yong Qin; Meng Li; Ming Yang; Xue-Ping Chen (Journal of Soils and Sediments, 2021)

How well do the ERA‐Interim , ERA ‐5, GLDAS ‐2.1 and NCEP‐R2 reanalysis datasets represent daily air temperature over the Tibetan Plateau? - Li Liu; Haiting Gu; Jingkai Xie; Yue‐Ping Xu (International Journal of Climatology, 2021)
Snow and glacier are important components in the hydrological cycle of the Tibetan Plateau (TP). Air temperature, as the main driver in freezing and thawing processes, becomes vital for hydrological modelling and prediction in this region. Due to a sparse ground gauging network, spatial density of air temperature measurement is insufficient for hydro‐meteorological studies. Therefore, the aim of this study is to identify the best representative temperature data for hydrological applications from four widely used reanalysis products, including ERA‐Interim, ERA‐5, GLDAS‐2.1 and NCEP‐R2, with reference to in situ measurements and gridded snow depth from the year 2008–2017 over the entire TP. To reduce errors, Bayesian Joint Probability (BJP) approach based on K‐Nearest Neighbour (KNN) classification algorithm (KNN‐BJP) is proposed to post‐process gridded reanalyses. The results indicate that all the reanalysis datasets provide highly correlated but cold biased air temperature. The correlation ecoefficiency is greater than 0.85. The cold biases are near −3 ° C and mainly distributed in the southeastern TP. Bias in daily maximum temperature during Spring is greater than −8 ° C for most stations. ERA‐Interim is found to have the closest agreement with in situ measurements, closely followed by GLDAS‐2.1. KNN‐BJP is found to be effective within a distance smaller than 5° . After post‐processing, the prominent underestimation is efficiently corrected with Bias near 0. RMSE is markedly reduced to be smaller than 2.5 ° C . The post‐processed ERA‐5 and GLDAS‐2.1 are as accurate as ERA‐Interim, but able to provide more detailed information for extreme events due to their finer spatial resolution. Thus, ERA‐5 and GLDAS‐2.1 are more recommended to represent air temperature in the TP. Snow depth as complementary reference data is able to present spatial variance of air temperature. Our study can help alleviate the problem of sparse air temperature data over the TP.

Reactive oxygen species altering the metabolite profile of the marine-derived fungus Dichotomomyces cejpii F31-1 - Sharpkate Shaker; Ting-Ting Sun; Liang-Yue Wang; Wen-Zhe Ma; Dong-Lan Wu; Yong-Wei Guo; Jun Dong; Yan-Xiu Chen; Long-Ping Zhu; De-Po Yang; Hou-Jin Li; Wen-Jian Lan (Natural Product Research, 2021)

Characterization of teaghrelin-like compounds from tea cultivars - Ping-Chung Kuo; Yue-Chiun Li; Ruo-Hsuan Wu; Jason T. C. Tzen (Natural Product Research, 2021)

Complete genome analysis of a novel iflavirus from a leaf beetle, Aulacophora lewisii - Zhuang-Xin Ye; Yue-Hong Li; Jian-Ping Chen; Chuan-Xi Zhang; Jun-Min Li (Archives of Virology, 2021)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

MdHAL3, a 4′-phosphopantothenoylcysteine decarboxylase, is involved in the salt tolerance of autotetraploid apple - Shuang Yang; Feng Zhang; Yangshu Wang; Hao Xue; Qiu Jiang; Jiajun Shi; Hongyan Dai; Zhihong Zhang; Linguang Li; Ping He; Yuanyuan Li; Yue Ma (Plant Cell Reports, 2020)

Population pharmacokinetics and dose optimization of ceftriaxone for children with community-acquired pneumonia - Muhammad Wasim Khan; Ya-Kun Wang; Yue-E Wu; Bo-Hao Tang; Min Kan; Hai-Yan Shi; Yi Zheng; Bao-Ping Xu; A-Dong Shen; Evelyne Jacqz-Aigrain; Li-Yuan Tian; Wei Zhao (European Journal of Clinical Pharmacology, 2020)

Effects of Increased Carbon Supply on the Growth, Nitrogen Metabolism and Photosynthesis of Vallisneria natans Grown at Different Temperatures - Heng Jiang; Bing Huang; Zhan Qian; Yue Xu; Xiaohong Liao; Ping Song; Xichun Li (Wetlands, 2020)

The protective effect of rosmarinic acid on myotube formation during myoblast differentiation under heat stress - Kun-Lin Chen; Yue Wang; Zhi-Ping Lin; Hui-Xia Li (In Vitro Cellular & Developmental Biology - Animal, 2020)

Characterization of Pneumocystis jirovecii pneumonia at three tertiary comprehensive hospitals in southern China - Yan-Hui Chen; Xue-Yao Fang; Yue-Ting Li; Yan-Ling Liu; Ya-Ping Hang; Yan-Ping Xiao; Xing-Wei Cao; Qiao-Shi Zhong; Long-Hua Hu (Brazilian Journal of Microbiology, 2020)

The bHLH gene family and its response to saline stress in Jilin ginseng, Panax ginseng C.A. Meyer - Lei Zhu; Mingzhu Zhao; Mengyao Chen; Li Li; Yue Jiang; Sizhang Liu; Yang Jiang; Kangyu Wang; Yanfang Wang; Chunyu Sun; Jing Chen; Ping Chen; et al. (Molecular Genetics and Genomics, 2020)

Biological Aerosol Particles in Polluted Regions - Wei Hu; Zihan Wang; Shu Huang; Lujie Ren; Siyao Yue; Ping Li; Qiaorong Xie; Wanyu Zhao; Lianfang Wei; Hong Ren; Libin Wu; Junjun Deng; et al. (Current Pollution Reports, 2020)

Lithic raw material economy at the Huayang site in Northeast China: localization and diversification as adaptive strategies in the Late Glacial - Jian-Ping Yue; You-Qian Li; Yu-Xiu Zhang; Shi-Xia Yang (Archaeological and Anthropological Sciences, 2020)
The study of lithic raw material plays an important role in developing archeologists’ understanding of the different adaptive strategies and behaviors of prehistoric people. In this paper, we present new evidence from the Huayang site that reveals lithic raw material procurement and exploitation strategies dating to around 14 ka cal. BP. The Huayang site is located in the southern portion of the Lesser Khingan Mountains in Northeast China, a key region for examining migration, diffusion, and interaction among hunter-gatherers in East and Northeast Asia. Our results indicate that diversified lithic raw materials were found and procured from local riverbeds and reduced at the site. Each raw material was reduced with distinctive knapping strategies and, as a result, there is a strong discrete spatial pattern for each of the different raw material types. Intra- and inter-site comparative analyses suggest a uniform trend towards localization and diversification of lithic raw materials in the southern Lesser Khingan Mountains, Northeast China during the Late Glacial, which seems to be associated with the paleoclimatic amelioration and the demographic expansion during this period.

Alternative complement pathway is activated in the brains of scrapie-infected rodents - Cao Chen; Yan Lv; Chao Hu; Xiao-Feng Xu; Ren-Qing Zhang; Kang Xiao; Yue Ma; Li-Ping Gao; Jian-Le Li; Qiang Shi; Jing Wang; Qi Shi; et al. (Medical Microbiology and Immunology, 2020)

Carbon Dots Doped with N and S towards Controlling Emitting - Tong Song; Yue Zhao; Tao Wang; Juping Li; Zhixiang Jiang; Ping Yang (Journal of Fluorescence, 2020)

Identification of cadmium-produced lipid hydroperoxides, transcriptomic changes in antioxidant enzymes, xenobiotic transporters, and pro-inflammatory markers in human breast cancer cells (MCF7) and protection with fat-soluble vitamins - Wageh Sobhy Darwish; Zhen Chen; Yonghan Li; Yue Wu; Hitoshi Chiba; Shu-Ping Hui (Environmental Science and Pollution Research, 2020)

Numerical Investigation on the Scale Effect of a Stepped Planing Hull - Lei Du; Zhuang Lin; Yi Jiang; Ping Li; Yue Dong (Journal of Marine Science and Engineering, 2019)
This article discusses the scale effects on a planing boat, utilizing the computational fluid dynamics method. The simulation is compared with a tank test for verification and validation. The planing boat sails use both aerodynamics and hydrodynamics. Studying the performances and wave patterns of different dimensions of the models is the best way to investigate the scale effect without using experimental data. The resistance is discussed in two parts, namely residuary resistance and friction resistance, and is compared to the calculated data using the international towing tank conference (ITTC) formula. The computational fluid dynamics (CFD) calculations of the model are increased by 4.77% on average, and the boat computations are also increased by 3.57%. The computation shows the scale effect in detail. The residuary resistance coefficients at different scales are approximately equal, and the friction resistance coefficients show the scale effect. The scale effect for longitudinal steadiness is also captured for the period of the porpoising behavior. The rational for the full-scaled boat oscillation period and the model is the root of the scales.

Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Song-mei Lou; Min Zhang; Zheng-rong Wu; Gui-xing Jiang; Hua Shen; Yi Dai; Yue-long Liang; Li-ping Cao; Guo-ping Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Development, Optimization, and Evaluation In Vitro/In Vivo of Oral Liquid System for Synchronized Sustained Release of Levodopa/Benserazide - Yang Qu; Wen-Long Lai; Yuan-Rong Xin; Fei-Qin Zhu; Yuan Zhu; Li Wang; Yue-ping Ding; Ying Xu; Hong-Fei Liu (AAPS PharmSciTech, 2019)

Three new labdane-type diterpenoids from Callicarpa macrophylla Vahl. - Zhen-Hui Wang; Huan-Jun Xu; Yang-Yang Zhai; Lan-Ping Yang; Qiang Li; Mei Huang; Xing-Ying Chen; Wen-Kui Zhang; Yue-Li Meng; Qing-Ling Zhang; Chao Niu; Yan-Ru Zhang (Natural Product Research, 2019)

Evaluation of TIGGE Daily Accumulated Precipitation Forecasts over the Qu River Basin, China - Li Liu; Chao Gao; Qian Zhu; Yue-Ping Xu (Journal of Meteorological Research, 2019)

Numerical Analysis on the Effect of Artificial Ventilated Pipe Diameter on Hydrodynamic Performance of a Surface-Piercing Propeller - Zeyang Gao; Dongmei Yang; Ping Li; Yue Dong (Journal of Marine Science and Engineering, 2019)
Under the condition of large water immersion, surface-piercing propellers are inclined to be heavy loaded. In order to improve the hydrodynamic performance of the surface-piercing propeller, the installation of a vent pipe in front of a propeller disc is more widely used in the propulsion device of high speed planning crafts. Based on computational fluid dynamics (CFD) method, this paper studied the influence of diverse vent pipe diameters on hydrodynamic performance of the surface-piercing propeller under full water immersion conditions. The numerical results show that, with the increase of vent pipe diameters, the thrust and torque of the surface-piercing propeller decrease after ventilation, and the efficiency of the propeller increases rapidly; the low pressure area near the back root of the blade becomes smaller and smaller gradually; and the peak of periodic vibration of thrust and torque can be effectively reduced. The numerical results demonstrate that the installation of artificial vent pipe effectively improves the hydrodynamic performance of surface piercing propeller in the field of high speed crafts, and the increase of artificial vent pipe diameter plays an active role in the propulsion efficiency of the surface-piercing propeller.

Molecular properties and immunomodulatory activities of a water-soluble heteropolysaccharide isolated from Plantago asiatica L. leaves - Jun-Yi Yin; Xin-Yue Huang; Li Wang; Jian-Qi Guo; Ming-Yong Xie; Jian-Yong Wu; Shao-Ping Nie (Natural Product Research, 2019)

Joint inversion method for interval quality factor based on amplitude and phase information - Dan-Ping Cao; Yue Li; Wen-Guo Sun; Kai Liang (Applied Geophysics, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Pond-bottom decomposition of leaf litters canopied by free-floating vegetation - Ya-Lin Zhang; Hong-Bin Li; Li Xu; Xu Pan; Wen-Bing Li; Jian Liu; Yue-Ping Jiang; Yao-Bin Song; Ming Dong (Environmental Science and Pollution Research, 2019)

Plantlet regeneration from primary callus cultures of Lilium brownii F.E.Br. ex Miellez var. giganteum G. Y. Li & Z. H. Chen, a rare bulbous germplasm - Yun Wu; Yi-Di Ma; Yue Li; Lin Zhang; Yi-Ping Xia (In Vitro Cellular & Developmental Biology - Plant, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Apolipoprotein E Exerts a Whole-Brain Protective Property by Promoting M1? Microglia Quiescence After Experimental Subarachnoid Hemorrhage in Mice - Jinwei Pang; Jianhua Peng; Nathanael Matei; Ping Yang; Li Kuai; Yue Wu; Ligang Chen; Michael P. Vitek; Fengqiao Li; Xiaochuan Sun; John H. Zhang; Yong Jiang (Translational Stroke Research, 2018)

Laminar Distribution of Neurochemically-Identified Interneurons and Cellular Co-expression of Molecular Markers in Epileptic Human Cortex - Qiyu Zhu; Wei Ke; Quansheng He; Xiongfei Wang; Rui Zheng; Tianfu Li; Guoming Luan; Yue-Sheng Long; Wei-Ping Liao; Yousheng Shu (Neuroscience Bulletin, 2018)

An inversion of transient electromagnetic data from a conical source - Hai-Yan Yang; Feng-Ping Li; Shen-En Chen; Jian-Hua Yue; Fu-Sheng Guo; Xiao Chen; Hua Zhang (Applied Geophysics, 2018)

Altered Profiles of Gut Microbiota in Klebsiella pneumoniae-Induced Pyogenic Liver Abscess - Nan Chen; Zong-Xin Ling; Tong-Tong Jin; Ming Li; Sheng Zhao; Li-Shuang Zheng; Xin Xi; Lin-Lin Wang; Ying-Ying Chen; Yue-Liang Shen; Li-Ping Zhang; Shao-cong Sun (Current Microbiology, 2018)

Joint structural and physiological control on the interannual variation in productivity in a temperate grassland: A data‐model comparison - Zhongmin Hu; Hao Shi; Kaili Cheng; Ying‐Ping Wang; Shilong Piao; Yue Li; Li Zhang; Jianyang Xia; Lei Zhou; Wenping Yuan; Steve Running; Longhui Li; et al. (Global Change Biology, 2018)
Given the important contributions of semiarid region to global land carbon cycle, accurate modeling of the interannual variability (IAV) of terrestrial gross primary productivity (GPP) is important but remains challenging. By decomposing GPP into leaf area index (LAI) and photosynthesis per leaf area (i.e., GPP_leaf), we investigated the IAV of GPP and the mechanisms responsible in a temperate grassland of northwestern China. We further assessed six ecosystem models for their capabilities in reproducing the observed IAV of GPP in a temperate grassland from 2004 to 2011 in China. We observed that the responses to LAI and GPP_leaf to soil water significantly contributed to IAV of GPP at the grassland ecosystem. Two of six models with prescribed LAI simulated of the observed IAV of GPP quite well, but still underestimated the variance of GPP_leaf, therefore the variance of GPP. In comparison, simulated pattern by the other four models with prognostic LAI differed significantly from the observed IAV of GPP. Only some models with prognostic LAI can capture the observed sharp decline of GPP in drought years. Further analysis indicated that accurately representing the responses of GPP_leaf and leaf stomatal conductance to soil moisture are critical for the models to reproduce the observed IAV of GPP_leaf. Our framework also identified that the contributions of LAI and GPP_leaf to the observed IAV of GPP were relatively independent. We conclude that our framework of decomposing GPP into LAI and GPP_leaf has a significant potential for facilitating future model intercomparison, benchmarking and optimization should be adopted for future data‐model comparisons.

Avian influenza viruses (AIVs) H9N2 are in the course of reassorting into novel AIVs - Hui-ping Chang; Li Peng; Liang Chen; Lu-fang Jiang; Zhi-jie Zhang; Cheng-long Xiong; Gen-ming Zhao; Yue Chen; Qing-wu Jiang (Journal of Zhejiang University-SCIENCE B, 2018)

A new pair of enantiomeric lignans from the fruits of Morinda citrifolia and their absolute configuration - Wen-Jian Liu; Yue-Juan Chen; Dan-Na Chen; Ya-Ping Wu; Yu-Jie Gao; Jing Li; Wen-Jun Zhong; Lin Jiang (Natural Product Research, 2018)

A Semi-analytical Model for Pressure-Dependent Permeability of Tight Sandstone Reservoirs - Su-Yang Zhu; Zhi-Min Du; Chuan-Liang Li; Alireza Salmachi; Xiao-Long Peng; Chao-Wen Wang; Ping Yue; Peng Deng (Transport in Porous Media, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Rock strata movement and subsidence based on MDDA, an improved discontinuous deformation analysis method in mining engineering - Jian-ping Zuo; Yun-jiang Sun; Yue-chun Li; Jin-tao Wang; Xu Wei; Long Fan (Arabian Journal of Geosciences, 2017)

Increasing the yield of middle silk gland expression system through transgenic knock-down of endogenous sericin-1 - Sanyuan Ma; Xiaojuan Xia; Yufeng Li; Le Sun; Yue Liu; Yuanyuan Liu; Xiaogang Wang; Run Shi; Jiasong Chang; Ping Zhao; Qingyou Xia (Molecular Genetics and Genomics, 2017)

A live gI/gE-deleted pseudorabies virus (PRV) protects weaned piglets against lethal variant PRV challenge - Yue Yin; Zhiwen Xu; Xiaowan Liu; Ping Li; Fan Yang; Jun Zhao; Yi Fan; Xiangang Sun; Ling Zhu (Virus Genes, 2017)

Isolation and characterisation of the epothilone gene cluster with flanks from high alkalotolerant strain Sorangium cellulosum (So0157-2) - Zhi-Feng Li; Li-Ping Zhu; Jing-yan Gu; Raghvendra Pratap Singh; Yue-Zhong Li (World Journal of Microbiology and Biotechnology, 2017)

Increases of Galectin-1 and its S-nitrosylated form in the Brain Tissues of Scrapie-Infected Rodent Models and Human Prion Diseases - Yan-Jun Guo; Qi Shi; Xiao-Dong Yang; Jian-Le Li; Yue Ma; Kang Xiao; Cao Chen; Jun Han; Xiao-Ping Dong (Molecular Neurobiology, 2017)

Environmental change and raw material selection strategies at Taoshan: a terminal Late Pleistocene to Holocene site in north‐eastern China - Shi‐Xia Yang; Yu‐Xiu Zhang; You‐Qian Li; Chao Zhao; Xiao‐Qiang Li; Jian‐Ping Yue; Ya‐Mei Hou; Cheng‐Long Deng; Ri‐Xiang Zhu; Michael D. Petraglia (Journal of Quaternary Science, 2017)
The Lesser Khingan Mountains of north‐eastern China are heavily forested, making archaeological site identification difficult owing to poor ground surface visibility. Nevertheless, several prehistoric archaeological site discoveries have been made in recent years and a limited number of excavations have been initiated. One of the most important sites to emerge is Taoshan, which has yielded stratified stone tool assemblages dating from the Last Glacial Maximum (LGM) to the mid‐Holocene. Pollen profiles indicate significant changes in vegetation, fluctuating from steppe conditions during the LGM to forested conditions in the Bølling–Allerød interstadial (B–A) and the mid‐Holocene. The stone tool assemblages from Taoshan were primarily produced from varieties of volcanic tuff, rhyolite, hornfels and agate. Geological prospecting and petrological analyses were performed to document procurement sources and changes in raw material exploitation strategies. During the LGM, the predominant raw material was vitric tuff, available from a source ca. 5–10 km from Taoshan. In the B–A and mid‐Holocene layers, emphasis was on the exploitation of raw materials in gravel bars, although stone tool reduction techniques and raw material preferences changed considerably during this time interval. Diachronic changes in raw materials and exploitation strategies correspond to changes in vegetation and human adaptations.

Inhibition of Blood-Brain Barrier Disruption by an Apolipoprotein E-Mimetic Peptide Ameliorates Early Brain Injury in Experimental Subarachnoid Hemorrhage - Jinwei Pang; Yitian Chen; Li Kuai; Ping Yang; Jianhua Peng; Yue Wu; Yue Chen; Michael P. Vitek; Ligang Chen; Xiaochuan Sun; Yong Jiang (Translational Stroke Research, 2017)

Serum Protein-Based Profiles as Novel Biomarkers for the Diagnosis of Alzheimer’s Disease - Shu Yu; Yue-Ping Liu; Hai-Liang Liu; Jie Li; Yang Xiang; Yu-Hui Liu; Shu-Sheng Jiao; Lu Liu; Yajiang Wang; Weiling Fu (Molecular Neurobiology, 2017)

One new lignan derivative from the Combretum alfredii Hance - Meng Bai; Li-Jun Wu; Yue Cai; Shou-Yuan Wu; Xiao-Ping Song; Guang-Ying Chen; Cai-Juan Zheng; Chang-Ri Han (Natural Product Research, 2017)

Astragaloside IV, a Natural PPARγ Agonist, Reduces Aβ Production in Alzheimer’s Disease Through Inhibition of BACE1 - Xu Wang; Yue Wang; Jiang-Ping Hu; Song Yu; Bao-Kun Li; Yong Cui; Lu Ren; Li-De Zhang (Molecular Neurobiology, 2017)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

Cone-shaped source characteristics and inductance effect of transient electromagnetic method - Hai-Yan Yang; Feng-Ping Li; Jian-Hua Yue; Fu-Sheng Guo; Xu-Hua Liu; Hua Zhang (Applied Geophysics, 2017)

Effects of zinc application rate and zinc distribution relative to root distribution on grain yield and grain Zn concentration in wheat - Dun-Yi Liu; Wei Zhang; Li-Li Pang; Yue-Qiang Zhang; Xiao-Zhong Wang; Yu-Min Liu; Xin-Ping Chen; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2017)

Morphological and molecular study of Longicollum pagrosomi Yamaguti, 1935 (Acanthocephala: Pomphorhynchidae) from the barred knifejaw Oplegnathus fasciatus (Temminck & Schlegel) (Perciformes: Oplegnathidae) in the East China Sea - Liang Li; Yue Yang; Lu-Ping Zhang (Systematic Parasitology, 2017)

NF-κB is involved in the LPS-mediated proliferation and apoptosis of MAC-T epithelial cells as part of the subacute ruminal acidosis response in cows - Wen-Jie Fan; He-Ping Li; He-Shui Zhu; Shi-Ping Sui; Pei-Ge Chen; Yue Deng; Tong-Ming Sui; Yue-Ying Wang (Biotechnology Letters, 2016)

Ancient DNA analysis of Panicum miliaceum (broomcorn millet) from a Bronze Age cemetery in Xinjiang, China - Chunxiang Li; Yu Dong; Minxuan Liu; Ping Lu; Wenying Li; Yingnan Wang; Xiyan Cui; Hui Zhou; Yue Xu (Vegetation History and Archaeobotany, 2016)

Microbial acclimation triggered loss of soil carbon fractions in subtropical wetlands subjected to experimental warming in a laboratory study - Hang Wang; HongYi Li; Fan Ping; ChunLei Yue; ZhiJian Zhang (Plant and Soil, 2016)

Genome-wide identification and characterization of the Dof gene family in moso bamboo (Phyllostachys heterocycla var. pubescens) - Tao Wang; Jin-Jun Yue; Xue-Ji Wang; Lu Xu; Lu-Bin Li; Xiao-Ping Gu (Genes & Genomics, 2016)

PD-1/PD-L1 signal pathway participates in HCV F protein-induced T cell dysfunction in chronic HCV infection - Wen Xiao; Long Feng Jiang; Xiao Zhao Deng; Dan Yan Zhu; Jia Ping Pei; Mao Lei Xu; Bing Jun Li; Chang Jun Wang; Jing Hai Zhang; Qi Zhang; Zhen Xian Zhou; Wei Liang Ding; et al. (Immunologic Research, 2016)

Effects of surfactants on low-molecular-weight organic acids to wash soil zinc - Yue Chen; Shirong Zhang; Xiaoxun Xu; Ping Yao; Ting Li; Guiyin Wang; Guoshu Gong; Yun Li; Ouping Deng (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

CD147 promotes IKK/IκB/NF-κB pathway to resist TNF-induced apoptosis in rheumatoid arthritis synovial fibroblasts - Yue Zhai; Bo Wu; Jia Li; Xi-ying Yao; Ping Zhu; Zhi-nan Chen (Journal of Molecular Medicine, 2016)

Retraction Note to: Relationships between PON1 Q192R polymorphism and clinical outcome of antiplatelet treatment after percutaneous coronary intervention: a meta-analysis - Ping Li; Shu-Hong Bu; Xiao-Tong Lu; Li-Xia Li; A-Jing Xu; Yue-Nian Tang; Jian Zhang (Molecular Biology Reports, 2015)

Turbulence intensity and turbulent kinetic energy parameters over a heterogeneous terrain of Loess Plateau - Ping Yue; Qiang Zhang; Runyuan Wang; Yaohui Li; Sheng Wang (Advances in Atmospheric Sciences, 2015)

Elevated Serum Homocysteine (Hcy) Levels May Contribute to the Pathogenesis of Cerebral Infarction - Hong-Juan Fu; Li-Bo Zhao; Ju-Jun Xue; Zhi-Xuan Wu; Yue-Ping Huang; Wei Liu; Zhan Gao (Journal of Molecular Neuroscience, 2015)

Soil organic matter fractions under different vegetation types in permafrost regions along the Qinghai-Tibet Highway, north of Kunlun Mountains, China - Wen Shang; Lin Zhao; Xiao-dong Wu; Yu-qiang Li; Guang-yang Yue; Yong-hua Zhao; Yong-ping Qiao (Journal of Mountain Science, 2015)

Association between PPAR-γ2 Pro12Ala polymorphism and obesity: a meta-analysis - Ying-shui Yao; Jie Li; Yue-long Jin; Yan Chen; Lian-ping He (Molecular Biology Reports, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

Characterization of mineralogy and surface zeta potential of atmospheric dust fall in northwest China - Fa-Qin Dong; Wu Chen; Qun-Wei Dai; Yue-Quan Deng; Ping He; Xiao-Chun He; Jun Tang; Li-Zhu Liu; Hua He (Mineralogy and Petrology, 2015)

Intranasal administration with recombinant Lactococcus lactis expressing heme oxygenase-1 reduces hyperoxia-induced lung inflammation in rat pups - Chang-Yi Wu; Luis G. Bermúdez-Humarán; Feng Yue; Min Li; Li-Ping Zhang (Biotechnology Letters, 2015)

The host HLA-A*02 allele is associated with the response to pegylated interferon and ribavirin in patients with chronic hepatitis C virus infection - Meng Wang; Jian-sheng Li; Yu Ping; Zhi-qin Li; Li-ping Wang; Qian Guo; Zhen Zhang; Dong-li Yue; Fei Wang; Teng-fei Zhang; Mohammad Serajul Islam; Yi Zhang (Archives of Virology, 2015)

Response of alpine grassland to elevated nitrogen deposition and water supply in China - Kaihui Li; Xuejun Liu; Ling Song; Yanming Gong; Chunfang Lu; Ping Yue; Changyan Tian; Fusuo Zhang (Oecologia, 2015)

Removal and Recovery of U(VI) from Low Concentration Radioactive Wastewater by Ethylenediamine-Modified Biomass of Aspergillus niger - De Xin Ding; Xin Xin; Le Li; Nan Hu; Guang Yue Li; Yong Dong Wang; Ping Kun Fu (Water, Air, & Soil Pollution, 2014)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Erratum to: Identification of a novel mutation in a Chinese family with Nance-Horan syndrome by whole exome sequencing - Nan Hong; Yan-hua Chen; Chen Xie; Bai-sheng Xu; Hui Huang; Xin Li; Yue-qing Yang; Ying-ping Huang; Jian-lian Deng; Ming Qi; Yang-shun Gu (Journal of Zhejiang University-SCIENCE B, 2014)

Bio-beads with immobilized anaerobic bacteria, zero-valent iron, and active carbon for the removal of trichloroethane from groundwater - Ya-Zhen Zhou; Jie Yang; Xiao-Li Wang; Yue-Qing Pan; Hui Li; Dong Zhou; Yong-Di Liu; Ping Wang; Ji-Dong Gu; Qiang Lu; Yue-Feng Qiu; Kuang-Fei Lin (Environmental Science and Pollution Research, 2014)

The Melanogenesis-Inhibitory Effect and the Percutaneous Formulation of Ginsenoside Rb1 - Lin Wang; Ai-Ping Lu; Zhi-Ling Yu; Ricky N. S. Wong; Zhao-Xiang Bian; Hoi-Hin Kwok; Patrick Ying-Kit Yue; Li-Min Zhou; HuBiao Chen; Min Xu; Zhijun Yang (AAPS PharmSciTech, 2014)

RETRACTED ARTICLE: Relationships between PON1 Q192R polymorphism and clinical outcome of antiplatelet treatment after percutaneous coronary intervention: a meta-analysis - Ping Li; Shu-Hong Bu; Xiao-Tong Lu; Li-Xia Li; A-Jing Xu; Yue-Nian Tang; Jian Zhang (Molecular Biology Reports, 2014)

Biofilm Formation of Streptococcus equi ssp. zooepidemicus and Comparative Proteomic Analysis of Biofilm and Planktonic Cells - Li Yi; Yang Wang; Zhe Ma; Hui Zhang; Yue Li; Jun-xi Zheng; Yong-chun Yang; Hong-jie Fan; Cheng-ping Lu (Current Microbiology, 2014)

Promoters of HcTPS1 and HcTPS2 Genes from Hedychium coronarium Direct Floral-Specific, Developmental-Regulated and Stress-Inducible Gene Expression in Transgenic Tobacco - Xin-Yue Li; Shao-Yuan Zheng; Rang-Cai Yu; Yan-Ping Fan (Plant Molecular Biology Reporter, 2014)

Identification of a novel mutation in a Chinese family with Nance-Horan syndrome by whole exome sequencing - Nan Hong; Yan-hua Chen; Chen Xie; Bai-sheng Xu; Hui Huang; Xin Li; Yue-qing Yang; Ying-ping Huang; Jian-lian Deng; Ming Qi; Yang-shun Gu (Journal of Zhejiang University-SCIENCE B, 2014)

Enhancement of nitrogen and phosphorus removal from eutrophic water by economic plant annual ryegrass (Lolium multiflorum) with ion implantation - Miao Li; Guo-ping Sheng; Yue-jin Wu; Zeng-liang Yu; Gary S. Bañuelos; Han-qing Yu (Environmental Science and Pollution Research, 2014)

Genetic Diversity and Population Structure of Seedling Populations of Pyrus pashia - Yu Zong; Ping Sun; Jing Liu; Xiaoyan Yue; Kunming Li; Yuanwen Teng (Plant Molecular Biology Reporter, 2014)

New eudesmane-type sesquiterpenoid from Solanum lyratum with cytotoxic activity - Xiu-Ping Nie; Fang Yao; Xi-Dian Yue; Gui-Sheng Li; Sheng-Jun Dai (Natural Product Research, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Endothelial Insulin-Like Growth Factor-1 Modulates Proliferation and Phenotype of Smooth Muscle Cells Induced by Low Shear Stress - Lu Wang; Yue Han; Yan Shen; Zhi-Qiang Yan; Ping Zhang; Qing-Ping Yao; Bao-Rong Shen; Li-Zhi Gao; Ying-Xin Qi; Zong-Lai Jiang (Annals of Biomedical Engineering, 2014)

Interaction Between AT1 Receptor and NF-κB in Hypothalamic Paraventricular Nucleus Contributes to Oxidative Stress and Sympathoexcitation by Modulating Neurotransmitters in Heart Failure - Xiao-Jing Yu; Yu-Ping Suo; Jie Qi; Qing Yang; Hui-Hua Li; Dong-Mei Zhang; Qiu-Yue Yi; Jian Zhang; Guo-Qing Zhu; Zhiming Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2013)

Overweight and Obesity Associated With Increased Total Serum Calcium Level: Comparison of Cross-sectional Data in the Health Screening for Teaching Faculty - Xiao-hua Ren; Ying-shui Yao; Lian-ping He; Yue-long Jin; Wei-wei Chang; Jie Li; Yan Chen; Xiu-li Song; Hui Tang; Ling-ling Ding; Dao-xia Guo; Chao-ping Li (Biological Trace Element Research, 2013)

New cycloartane triterpene glycosides from Beesia calthaefolia - Hong-Jie Li; Li-Hua Mu; Xian-Zhe Dong; Xiao-Yue Ge; Ping Liu (Natural Product Research, 2013)

Genetic phylogeography and maternal lineages of 18 Chinese black goat breeds - Tao Zhong; Qian Jun Zhao; Li Li Niu; Jie Wang; Peng Fei Jin; Wei Zhao; Lin Jie Wang; Li Li; Hong Ping Zhang; Yue Hui Ma (Tropical Animal Health and Production, 2013)

Design, synthesis and antidepressant activity evaluation 2′-hydroxy-4′,6′-diisoprenyloxychalcone derivatives - Li-Ping Guan; Dong-Hai Zhao; Yue Chang; Yu Sun; Xiao-Li Ding; Jing-Fei Jiang (Medicinal Chemistry Research, 2013)

RNA interference mediated pten knock-down inhibit the formation of polycystic ovary - Jie-Xiu Ouyang; Tao Luo; Hui-Yun Sun; Jian Huang; Dan-Feng Tang; Lei Wu; Yue-Hui Zheng; Li-Ping Zheng (Molecular and Cellular Biochemistry, 2013)

Geochemistry and Sr–Nd–Pb–Hf isotopic composition of the Donggou Mo-bearing granite porphyry, Qinling orogenic belt, central China - Li Yang; Fukun Chen; Bing-Xiang Liu; Zhao-Ping Hu; Yue Qi; Jia-De Wu; Jian-Feng He; Wolfgang Siebel (International Geology Review, 2013)

Expression of yeast acyl-CoA-∆9 desaturase leads to accumulation of unusual monounsaturated fatty acids in soybean seeds - Jin-Ai Xue; Xue Mao; Zhi-Rong Yang; Yong-Mei Wu; Xiao-Yun Jia; Li Zhang; Ai-Qin Yue; Ji-Ping Wang; Run-Zhi Li (Biotechnology Letters, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Analysis of B-Class Genes NAP3L3 and NAP3L4 in Narcissus tazetta var. chinensis - Xiao-Fang Li; Jing Xu; Ru Yang; Lin-Yan Jia; Xin-Jie Deng; Li-Jun Xiong; Xue-Ping Zhang; Qi Fang; Wei Zhang; Yue Sun; Ling Xu (Plant Molecular Biology Reporter, 2013)

Drought stress induces oxidative stress and the antioxidant defense system in ascorbate-deficient vtc1 mutants of Arabidopsis thaliana - Yue Niu; Yuping Wang; Ping Li; Feng Zhang; Heng Liu; Guochang Zheng (Acta Physiologiae Plantarum, 2013)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

Molecular diversity of restriction enzyme sites, Indels and upstream open reading frames (uORFs) of 5′ untransalted regions (UTRs) of Waxy genes in Triticum L. and Aegilops L. species - Wei Li; Zhen Gao; Wei Xiao; Yu-Ming Wei; Ya-Xi Liu; Guo-Yue Chen; Zhi-En Pu; Hua-Ping Chen; You-Liang Zheng (Genetic Resources and Crop Evolution, 2012)

Traditional Chinese medicines benefit to nonalcoholic fatty liver disease: a systematic review and meta-analysis - Ke-Qing Shi; Yu-Chen Fan; Wen-Yue Liu; Ling-Fei Li; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Pseudolaric acid B-driven phosphorylation of c-Jun impairs its role in stabilizing HIF-1alpha: a novel function-converter model - Bing Yu; Mei-Hong Li; Wei Wang; Ying-Qing Wang; Yi Jiang; Sheng-Ping Yang; Jian-Min Yue; Jian Ding; Ze-Hong Miao (Journal of Molecular Medicine, 2012)

Synthesis and studies on antidepressant activity of 2′,4′,6′-trihydroxychalcone derivatives - Xin Sui; Ying-Chun Quan; Yue Chang; Rui-Peng Zhang; Yin-Feng Xu; Li-Ping Guan (Medicinal Chemistry Research, 2012)

Polymorphisms in luteinizing hormone receptor and hypothalamic gonadotropin-releasing hormone genes and their effects on sperm quality traits in Chinese Holstein bulls - Li-Ping Sun; Qing-Zhi Du; Ya-Pan Song; Jun-Na Yu; Shu-Juan Wang; Lei Sang; Luo-Wen Song; Yao-Min Yue; Yu-Ze Lian; Sheng-Li Zhang; Guo-Hua Hua; Shu-Jun Zhang; et al. (Molecular Biology Reports, 2012)

Human anti-EGFL7 recombinant full-length antibodies selected from a mammalian cell-based antibody display library - Feng Li; Yan-Hong Liu; Yan-Wen Li; Qian Ju; Lin Chen; Ping-Li Xie; Yue-Hui Li; Guan-Cheng Li (Molecular and Cellular Biochemistry, 2012)

Characterization of the Hormone and Stress-Induced Expression of FaRE1 Retrotransposon Promoter in Strawberry - Ping He; Yue Ma; Hongyan Dai; Linguang Li; Yuexue Liu; He Li; Guiling Zhao; Zhihong Zhang (Journal of Plant Biology, 2012)

Genetic structure of three fosmid‐fragments encoding 16S rRNA genes of the Miscellaneous Crenarchaeotic Group (MCG): implications for physiology and evolution of marine sedimentary archaea - Ping‐Yi Li; Bin‐Bin Xie; Xi‐Ying Zhang; Qi‐Long Qin; Hong‐Yue Dang; Xu‐Min Wang; Xiu‐Lan Chen; Jun Yu; Yu‐Zhong Zhang (Environmental Microbiology, 2012)
Summary Archaea of the Miscellaneous Crenarchaeotic Group (MCG) exist widely in soil, freshwater and marine sediments of both surface and subsurface. However, current knowledge about this group is limited to its phylogenetic diversity. An archaeal 16S library was constructed from a sediment sample from the South China Sea, which was dominated by MCG and Marine Group I (MG‐I). A metagenomic library was constructed from the same sediment sample, and three MCG fosmids (E6‐3G, E37‐7F and E48‐1C) containing 16S rRNA genes were screened. Annotation showed that the three genomic fragments encode a variety of open reading frames (ORFs) that are potentially homologous to important functional genes related to lipid biosynthesis, energy metabolism, and resistance to oxidants. No colinear regions were found between MCG fosmids and reported archaeal genomic fragments or genomes, suggesting that the MCG archaea are quite different from the sequenced archaea in gene arrangement. Analyses of both the phylogenies of 16S rRNA genes and several informational processing genes and nucleotide frequencies showed that MCG archaea are distinct from MG‐I plus relatives. In addition, tetranucleotide frequency analysis in combination with phylogenetic analysis suggested that some fragments in the MCG fosmids are probably derived from non‐MCG or non‐archaeal genomes.

Erratum to: Effects of proNGF on Neuronal Viability, Neurite Growth and Amyloid-beta Metabolism - Yan-Jiang Wang; Deborah Valadares; Ying Sun; Xin Wang; Jin-Hua Zhong; Xiao-Hong Liu; Shohreh Majd; Li Chen; Chang-Yue Gao; Si Chen; Yoon Lim; Anthony Pollard; et al. (Neurotoxicity Research, 2011)

Human amniotic fluid-derived stem cells can differentiate into hepatocyte-like cells in vitro and in vivo - Hui Liu; Da-qing Liu; Bao-wei Li; Li-dong Guan; Zhi-feng Yan; Ya-li Li; Xue-tao Pei; Wen Yue; Min Wang; Yan-ping Lu; Hong-mei Peng; Yang Lv (In Vitro Cellular & Developmental Biology - Animal, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Development and application of an efficient virus-induced gene silencing system in Nicotiana tabacum using geminivirus alphasatellite - Chang-jun Huang; Tong Zhang; Fang-fang Li; Xin-yue Zhang; Xue-ping Zhou (Journal of Zhejiang University-SCIENCE B, 2011)

Protein structure alignment based on internal coordinates - Yue-Feng Shen; Bo Li; Zhi-Ping Liu (Interdisciplinary Sciences: Computational Life Sciences, 2010)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

Characterization of human embryonic stem cell-derived hematopoietic progenitor phenotype - Hai-Yang Zhou; Xiao-Yi Yang; Li-Jian Tao; Yue-Tian Chang; Ru-Ping Dai (In Vitro Cellular & Developmental Biology - Animal, 2010)

FaRE1: a transcriptionally active Ty1-copia retrotransposon in strawberry - Ping He; Yue Ma; Guiling Zhao; Hongyan Dai; He Li; Linlin Chang; Zhihong Zhang (Journal of Plant Research, 2010)

Computed tomography angiography-guided percutaneous coronary intervention in chronic total occlusion - Ping Li; Lu-yue Gai; Xia Yang; Zhi-jun Sun; Qin-hua Jin (Journal of Zhejiang University-SCIENCE B, 2010)

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Fan-Rong Wu; Jian-Ping Li; Cheng-Wan Li; Yu Wang; Teng-Yue Zhang; Wei Hu (Molecular and Cellular Biochemistry, 2010)

Regulating A549 cells growth by ASO inhibiting miRNA expression - Ping-Yu Wang; You-Jie Li; Shuai Zhang; Zun-Ling Li; Zhen Yue; Ning Xie; Shu-Yang Xie (Molecular and Cellular Biochemistry, 2010)

Prestack Gaussian beam depth migration under complex surface conditions - Yu-Bo Yue; Zhen-Chun Li; Ping Zhang; Xue-Feng Zhou; Ning Qin (Applied Geophysics, 2010)

Effects of proNGF on Neuronal Viability, Neurite Growth and Amyloid-beta Metabolism - Yan-Jiang Wang; Deborah Valadares; Ying Sun; Xin Wang; Jin-Hua Zhong; Xiao-Hong Liu; Shohreh Majd; Li Chen; Chang-Yue Gao; Si Chen; Yoon Lim; Anthony Pollard; et al. (Neurotoxicity Research, 2010)

New pathotypes of Heterodera avenae (cereal cyst nematode) from winter wheat in Zhengzhou, Henan, China - Hong-xia Yuan; Jun-wei Sun; Wei-xing Yang; Xiao-ping Xing; Zhen-yue Wang; Ian T. Riley; Hong-lian Li (Australasian Plant Pathology, 2010)

Twelve novel microsatellite loci from an endangered marine fish species golden pompano Trachinotus blochii - Ping Gong; Jiale Li; Gen Hua Yue (Conservation Genetics, 2009)

Could nested PCR be applicable for the study of microbial diversity? - Zhen-Yu Fan; Xiao-Ran Li; Dan-Ping Mao; Gen-Feng Zhu; Sheng-Yue Wang; Zhe-Xue Quan (World Journal of Microbiology and Biotechnology, 2009)

Respiratory face mask: a novel and cost-effective device for use during the application of myocardial ischemia in rats - Yuan Yuan; Fei Li; Yue-min Wang; Rong-qing Zhang; Li-ping Wei; Hai-chang Wang (Journal of Zhejiang University-SCIENCE B, 2009)

Protective effects of N-acetylcysteine in isoproterenol-induced myocardium injury in rats - Bin Liu; Weimin Li; Yue Li; Zhonghua Wang; Hongli Li; Ping Liu; Jun Fu (Molecular Biology Reports, 2009)

Molecular Cloning, Expression, and Chromosomal Mapping of the Porcine CDC-2-Like Kinase 1 (CLK1) Gene - Shui Hua Xie; Jia Qi Li; Yao Sheng Chen; Ping Gao; Hao Zhang; Ze Yue Li (Biochemical Genetics, 2009)

Evaluation of antimicrobial activity of certain Chinese plants used in folkloric medicine - Airong Li; Yue Zhu; Xingbing He; Xingjun Tian; Liang Xu; Wu Ni; Ping Jiang (World Journal of Microbiology and Biotechnology, 2008)

Identification and expression analysis of hepcidin-like cDNAs from pigeon (Columba livia) - Yu Ming Fu; Su Ping Li; Yue Feng Wu; Yan Zhong Chang (Molecular and Cellular Biochemistry, 2007)

Identification and expression analysis of alternatively spliced isoforms of human interleukin-23 receptor gene in normal lymphoid cells and selected tumor cells - Xiang-Yue Zhang; Hai-Jing Zhang; Yun Zhang; Ying-Jie Fu; Jie He; Li-Ping Zhu; Shu-Hui Wang; Li Liu (Immunogenetics, 2006)

Genetic Differences between Wild and Artificial Populations of Metasequoia glyptostroboides : Implications for Species Recovery - YUAN‐YUAN LI; XIAO‐YONG CHEN; XIN ZHANG; TIAN‐YI WU; HUI‐PING LU; YUE‐WEI CAI (Conservation Biology, 2005)
Information on population genetics is fundamental to developing in situ or ex situ conservation strategies. Few researchers, however, have compared the genetic structure of restored and natural populations of threatened plant species. Metasequoia glyptostroboides Hu & Cheng (dawn redwood) (Taxodiaceae), a living fossil endemic to China, may be the most successfully recovered threatened species, with many more individuals and a much wider distribution than fossil records indicate. We used random amplification of polymorphic DNA markers to compare the genetic structure of artificial populations with that of wild ones and to determine whether the genetic structure of M. glyptostroboides has been recovered as has its distribution. The genetic variation of wild populations of M. glyptostroboides was lower than the average of gymnosperms, indicating the effects of glaciations and recent habitat loss and fragmentation. Genetic variation in artificial populations was less, but not substantially, compared with wild populations. The unweighted pair group method with arithmetic mean revealed that the wild and the artificial populations formed two distinct groups. Artificial populations were more similar to each other (mean Nei's genetic distance = 0.0924) than to wild populations (mean distance = 0.2054). This might be the result of biased seed collection, vegetative propagation, or a mixture of propagules from different populations and an ultimate propagule source. These results suggest that although the quantity and distribution range have been successfully restored, the genetic structure of M. glyptostroboides has not recovered appropriately, given the loss of genetic variation and biased genetic composition in artificial populations. Therefore, in addition to protecting the wild populations, additional ex situ genetic reserves should be established based on genetic knowledge and via appropriate approaches. We suggest that population genetic and demographic indices should be considered when downlisting or delisting threatened species.